Ultrasonic vibration thermal aging treatment method and high-performance aluminum-magnesium-silicon alloy material
By introducing ultrasonic mechanical vibration during the heat treatment of aluminum-magnesium-silicon alloys, the problems in the existing technology such as slow precipitation rate of strengthening phase, difficulty in controlling dislocation density, lack of grain refinement and insufficient microstructure uniformity are solved, achieving aluminum Efficient mechanical performance improvement and microstructure optimization of magnesium-silicon alloys.
Patent Information
- Application Number
- CN202411459869.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
During the heat treatment process of existing aluminum-magnesium silicon alloys, there are problems such as slow precipitation rate of reinforced phase, difficulty in regulating dislocation density, no grain refinement, and insufficient microstructure uniformity.
The ultrasonic coupling short-term thermal aging treatment method is adopted. By applying high-frequency vibration energy while heating and maintaining temperature, ultrasonic mechanical vibration is used to break the limitations of dislocations introduced by traditional plastic deformation and achieve rapid proliferation and uniform distribution of dislocations.
It significantly improves the mechanical properties and micro -structure uniformity of aluminum -magnesium and silicon alloy, shorten the timeliness time, improves the hardness and tensile strength, and realizes the rapid precipitation of the enhanced phase, the grain fineness and the density density.
Smart Images

Figure CN119351912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy heat treatment, and in particular relates to an ultrasonic vibration heat aging treatment method and a high-performance aluminum-magnesium-silicon alloy material. Background Art
[0002] In the existing technology, there are many problems in the methods of solid solution, aging, large plastic deformation, etc. of aluminum-magnesium-silicon alloy. Artificial aging often takes a long time and precipitation and transformation of precipitate phase will occur during the aging process. The precipitation sequence and transformation are generally: α-Al→GP zones→β"→β′→β-Mg2Si. In the early stage of aging, many solute atomic clusters GP zones that are completely coherent with the Al matrix appear. The precipitation of GP zones can further improve the hardness of the alloy. The presence of a large number of GP zones provides favorable conditions for the nucleation of β" phase. As the main strengthening phase in Al-Mg-Si alloy, β" phase is a nano-scale metastable precipitation phase composed of Mg and Si. Its chemical formula is Mg5Si6. It is also completely coherent with the aluminum matrix. After aging treatment to a certain extent, β" phase will transform into β' phase. Its chemical formula is Mg9Si5. It is in a semi-coherent state with the Al matrix and has weak strengthening ability. In the over-aging state, β' phase will transform into β-Mg2Si. β-Mg2Si is a stable phase and is in a non-coherent state with the matrix, so its strengthening ability is the weakest. Based on the characteristics of these phases that are easy to convert, the time and temperature of the aging process are difficult to control and often become the key factors affecting its performance.
[0003] Large plastic deformation is a relatively effective method, but this method has significant limitations in microstructure control and material strengthening: first, plastic deformation requires a large external force to effectively introduce a sufficient number of dislocations, which increases processing costs and difficulty; second, the distribution of dislocations generated during the deformation process is usually uneven, which makes it difficult to achieve the ideal dislocation density in a short time, and thus cannot fully improve the comprehensive performance of aluminum-magnesium-silicon alloys; third, the traditional method of introducing dislocations by deformation has an adverse effect on the processing performance and subsequent treatment of aluminum-magnesium-silicon alloys, such as causing surface defects, stress concentration and other problems. Therefore, how to accurately control the microstructure of aluminum-magnesium-silicon alloys such as dislocation density, grain size and precipitation phase in a short time to improve their comprehensive performance has become an unresolved problem. Summary of the invention
[0004] (I) Purpose of the invention: In order to solve the problem of difficulty in controlling dislocations in Al-Mg-Si alloys, the present invention proposes an ultrasonically coupled short-aging high-performance Al-Mg-Si alloy, an ultrasonic vibration thermal aging treatment method and a device. By introducing ultrasonic mechanical vibration, high-frequency vibration energy is applied while heating and heat preservation, breaking the limitation of introducing dislocations by deformation alone, achieving rapid proliferation and uniform distribution of dislocations in a relatively short time, and effectively improving the mechanical properties and microstructural uniformity of Al-Mg-Si alloys.
[0005] The first purpose of the present invention is to provide an aluminum-magnesium-silicon alloy ultrasonic vibration heat aging treatment method and an aluminum-magnesium-silicon alloy material. By coupling ultrasonic vibration with the heat treatment process, the rate of strengthening phase precipitation, the regulation of dislocation density and the grain refinement effect are significantly improved, thereby solving the problems of slow strengthening phase precipitation rate, difficult dislocation density control, no grain refinement and insufficient microstructure uniformity in the traditional aging treatment process.
[0006] The second purpose of the present invention is to provide a high-performance aluminum-magnesium-silicon alloy material formed by ultrasonic coupling short-aging. The hardness and tensile strength of the aluminum-magnesium-silicon alloy material are significantly improved by ultrasonic vibration aging treatment at 150°C for 3 hours, while maintaining good toughness and plasticity, and achieving rapid precipitation of strengthening phases, grain refinement, and increased dislocation density. The problems of poor strengthening effect, long aging treatment time, difficulty in microstructure control, and limited improvement in comprehensive mechanical properties of traditional aluminum-magnesium-silicon alloys in the heat treatment process of traditional aluminum-magnesium-silicon alloys are solved.
[0007] The third object of the present invention is to provide an ultrasonic aging vibration device, which uses a variable amplitude rod (3) to amplify the mechanical vibration amplitude, and a fixed frame (6) and a fixed base (5) to effectively suppress the displacement and shaking of the aluminum-magnesium-silicon alloy rod during the vibration process, thereby solving the problem that in conventional ultrasonic vibration equipment, energy is easily attenuated during the vibration transmission process, resulting in low vibration transmission efficiency.
[0008] (II) Technical solution: The present invention provides a thermal aging treatment method of high-performance aluminum-magnesium-silicon alloy by ultrasonic vibration with short aging time, comprising the following stages:
[0009] 1. Solution treatment (pretreatment 1): The coarse second phase in the rod-shaped aluminum-magnesium-silicon alloy matrix is fully dissolved at high temperature to form a supersaturated solid solution;
[0010] 2. Water-cooling quenching (pretreatment 2): through rapid cooling, the formation of precipitation phase is prevented, and the rod-shaped aluminum-magnesium-silicon alloy material is kept in a highly solid solution state after the solid solution treatment;
[0011] 3. Thermal aging treatment of ultrasonic mechanical vibration, which is subdivided into the period of introducing ultrasonic mechanical vibration and performing heating treatment, the period of thermal aging treatment, and the short-time coupling treatment;
[0012] 3.1 Heating treatment period: by introducing ultrasonic mechanical vibration during the heating process of 1-3 hours at 130℃-170℃, a coupled field of temperature + mechanical vibration is formed to regulate the generation and movement of dislocations, and further improve the microstructural properties of rod-shaped aluminum-magnesium-silicon alloy materials;
[0013] 3.2 Thermal aging treatment period: Through 1-3 hours, 130℃-170℃ thermal aging treatment, the maximum precipitation of β" strengthening phase is promoted, and the dislocation density is controlled by combining ultrasonic mechanical vibration to achieve microstructure optimization;
[0014] 3.3 Short-time coupling treatment: Through 1-3 hours, 130℃-170℃ short-time coupling treatment, under the action of temperature and ultrasonic mechanical vibration, the dislocation density is regulated and the grains are refined, and the microstructure is optimized to improve the overall performance of the rod-shaped aluminum-magnesium-silicon alloy material;
[0015] 4. Microstructure measurement (post-treatment): The dislocation density and microstructure of the rod-shaped aluminum-magnesium-silicon alloy material sample after treatment were observed by transmission electron microscopy (TEM), and the microstructure changes of the rod-shaped aluminum-magnesium-silicon alloy material obtained after treatment were measured.
[0016] The specific steps of introducing ultrasonic mechanical vibration and performing the heating treatment period are:
[0017] S1. Tapping treatment: Select an aluminum-magnesium-silicon alloy rod that has been water-cooled and quenched, with a length of 25 cm and a diameter of 12 mm. One end is tapped with a thread pitch of 1.75 mm to ensure that the ultrasonic transducer 2 can be firmly connected to the aluminum-magnesium-silicon alloy rod and the vibration is evenly transmitted;
[0018] S2. Surface cleaning: Ensure that the surface of the aluminum-magnesium-silicon alloy rod is clean and free of oxides or dirt to ensure a stable connection of the ultrasonic transducer (2) and uniform transmission of ultrasonic vibration;
[0019] S3. Prepare an ultrasonic aging vibration device: first select an ultrasonic generator 1 with a power of 100W and a vibration frequency of 20kHz, and check the state of the ultrasonic generator to ensure that the power and frequency settings meet the requirements and can operate normally; then select an ultrasonic transducer 2, and connect the ultrasonic transducer 2 to the ultrasonic generator 1; the vibration frequency of the ultrasonic transducer 2 should be 20kHz, and the diameter of the bottom threaded hole is 12mm, ensuring that the transducer 2 is intact and the vibration frequency is consistent; before the thermal aging treatment operation, check the connection of all cables and interfaces to ensure that they are not loose and the vibration signal is transmitted correctly;
[0020] S4. Prepare an ultrasonic aging vibration device for heating treatment: preheat the drying oven 4 to 150°C in advance to ensure that the temperature inside the drying oven 4 is uniform and stable and reaches the specified heating environment. Sufficient space should be reserved in the drying oven 4 to avoid direct contact between the aluminum-magnesium-silicon alloy rod and the box wall to ensure uniform heat conduction;
[0021] S5. Install, fix and connect the ultrasonic aging vibration device;
[0022] S6. Drying box) heating and introduction of ultrasonic vibration synchronous operation: During the heating process in the drying box 4, the aluminum-magnesium-silicon alloy rod is heated and vibrated synchronously at 150°C and 20kHz ultrasonic vibration; at the same time, the ultrasonic generator 1 is started to mechanically vibrate the aluminum alloy rod at a frequency of 20kHz; the time for simultaneous heating and ultrasonic vibration treatment is generally continued for 3 hours to ensure that the aluminum-magnesium-silicon alloy rod completes the maximum precipitation of the strengthening phase in a short time and regulates the dislocation through mechanical vibration;
[0023] S7. Natural cooling: turn off the ultrasonic generator 1 and take out the aluminum alloy rod, and wait for natural cooling; at this time, the dislocation density of the aluminum-magnesium-silicon alloy rod will be effectively controlled.
[0024] Furthermore, according to the above-mentioned ultrasonic vibration heat aging treatment method, the present invention obtains an ultrasonically coupled short-aging high-performance aluminum-magnesium-silicon alloy material with smooth morphology, refined and uniformly distributed grains, large amount of β" phase precipitation, small size and uniform distribution, very few β' phases and β phases, and significant dislocation density. The hardness of the obtained high-performance aluminum-magnesium-silicon alloy material reaches 120-125HV, and the tensile strength reaches 320-330MPa.
[0025] Furthermore, the invention discloses a method for thermal aging treatment of a high-performance aluminum-magnesium-silicon alloy with ultrasonic coupling and short aging time by ultrasonic vibration. The equipment used in the method is an ultrasonic aging vibration device.
[0026] The ultrasonic aging vibration device described in the present invention is composed of six parts: an ultrasonic generator 1, a transducer 2, a horn 3, a drying box 4, a fixed base 5 and a fixed frame 6; the ultrasonic generator 1 can convert an electrical signal into an ultrasonic signal; the transducer 2 can convert the received ultrasonic signal into a mechanical vibration with the same frequency. The lower end of the transducer 2 has a horn 3 for amplifying the mechanical vibration amplitude. The aluminum alloy rod is connected to the horn 3 and fixed in a drying box 4 with a fixed temperature; the horn 3 is used to amplify the mechanical vibration amplitude generated by the transducer 2 to ensure that the aluminum alloy rod It can withstand sufficiently strong mechanical vibration; the drying box 4 can maintain the temperature stability during the aging process; the fixed base 5 is used to support the aluminum-magnesium-silicon alloy rod to ensure that the rod remains stable during mechanical vibration and heat treatment, avoid displacement or shaking during vibration, and ensure that the vibration can be evenly transmitted to the entire aluminum-magnesium-silicon alloy rod; the fixed frame 6 can ensure that when the vibration is transmitted from the amplitude rod 3 to the aluminum-magnesium-silicon alloy rod, the ultrasonic vibration can be more effectively transmitted to the entire aluminum-magnesium-silicon alloy rod to enhance the uniformity of mechanical vibration inside the aluminum-magnesium-silicon alloy rod, thereby improving the vibration efficiency.
[0027] The ultrasonic aging vibration device of the present invention realizes efficient mechanical vibration and thermal aging treatment of aluminum-magnesium-silicon alloy bars by interconnecting and working in coordination; the specific structures of the six main components are as follows:
[0028] The ultrasonic generator 1 is a rectangular or cubic electronic device, which contains a circuit for generating high-frequency electrical signals; the ultrasonic generator 1 is installed on the top of the ultrasonic aging vibration device and connected to the transducer 2; the ultrasonic generator 1 is then connected to the transducer 2 through an electrical connection and a cable to send an ultrasonic signal; the ultrasonic generator 1 converts the electrical signal into an ultrasonic signal and transmits it to the horn 3 and the aluminum-magnesium-silicon alloy rod through the transducer 2;
[0029] The transducer 2 is cylindrical or rectangular, and contains a component that converts ultrasonic signals into mechanical vibrations. The transducer 2 is installed above the aluminum-magnesium-silicon alloy rod, connected to the ultrasonic generator 1 and the horn 3. The transducer 2 can receive the ultrasonic signal sent by the ultrasonic generator 1 and convert it into mechanical vibrations of the same frequency.
[0030] The horn 3 is located between the transducer 2 and the aluminum-magnesium-silicon alloy rod, connects the transducer 2 and the aluminum-magnesium-silicon alloy rod, and is used to amplify the mechanical vibration amplitude generated by the transducer 2;
[0031] The drying box 4 is rectangular or cubic, and has a heating element and a temperature control system inside to ensure a constant temperature; the drying box 4 is located at the lower part of the ultrasonic aging vibration device, and as an independent part, has no fixed connection with the aluminum-magnesium-silicon alloy rod, and the lower part of the aluminum-magnesium-silicon alloy rod is placed in the drying box 4; the interior of the drying box 4 surrounds the lower part of the aluminum-magnesium-silicon alloy rod to provide a thermal field environment;
[0032] The fixed base 5 is a stable square structure, located at the bottom of the ultrasonic aging vibration device, and is used to support the aluminum-magnesium-silicon alloy rod, ensuring contact with the aluminum-magnesium-silicon alloy rod but not limiting the longitudinal vibration freedom of the rod;
[0033] The fixed frame 6 is a rectangular metal structure located in the upper middle part of the aluminum-magnesium-silicon alloy rod and is used to limit the lateral shaking of the aluminum-magnesium-silicon alloy rod to ensure that the vibration can be evenly transmitted to the entire aluminum-magnesium-silicon alloy rod.
[0034] The ultrasonic aging vibration device is composed of six main parts: an ultrasonic generator 1, a transducer 2, a horn 3, a drying box 4, a fixed base 5 and a fixed frame 6. The overall connection relationship of the six parts is: the ultrasonic generator 1 is connected to the transducer 2, and the ultrasonic signal is transmitted to the transducer 2 through a cable connection; the transducer 2 is connected to the horn 3 through a threaded connection to ensure effective transmission of vibration; and then the horn 3 is connected to the aluminum-magnesium-silicon alloy rod through a threaded connection to ensure that the vibration is transmitted from the horn 3 to the aluminum-magnesium-silicon alloy rod; the lower end of the aluminum-magnesium-silicon alloy rod is placed on the fixed base 5 and placed in the drying box 4, and is kept stable by the fixed frame 6; the drying box 4 provides a constant temperature environment, surrounding the lower part of the aluminum-magnesium-silicon alloy rod, but has no mechanical connection with the aluminum-magnesium-silicon alloy rod.
[0035] The transmission method of the ultrasonic aging vibration device is as follows: the ultrasonic generator 1 converts the electrical signal into an ultrasonic signal and transmits it to the transducer 2; then the transducer 2 converts the ultrasonic signal into mechanical vibration, the amplitude transformer 3 amplifies the amplitude of the mechanical vibration and transmits it to the aluminum-magnesium-silicon alloy rod; the entire vibration process is completed through threaded connection and mechanical transmission.
[0036] The driving mode of the ultrasonic aging vibration device is as follows: the ultrasonic signal generated by the ultrasonic generator 1 drives the vibration of the aluminum-magnesium-silicon alloy rod through the transmission and amplification of mechanical vibration.
[0037] The overall operation process of the ultrasonic aging vibration device is as follows:
[0038] S1. High-frequency ultrasonic generation: ultrasonic generator 1 generates a high-frequency ultrasonic signal;
[0039] S2. Signal conversion: Transducer 2 receives the ultrasonic signal and converts the ultrasonic signal into mechanical vibration of the same frequency;
[0040] S3. Vibration amplification: The horn 3 amplifies the amplitude of the mechanical vibration generated by the transducer 2;
[0041] S4. Vibration transmission: Mechanical vibration is transmitted to the aluminum-magnesium-silicon alloy rod through the horn 3;
[0042] S5. Thermal field coupling: The aluminum-magnesium-silicon alloy rod is subjected to a constant temperature environment provided by the drying oven 4 while undergoing mechanical vibration, thereby forming a coupling field of mechanical vibration and heat treatment;
[0043] S6. Structural optimization: Under the combined effects of mechanical vibration and heat treatment, the microstructural changes such as dislocation movement, strengthening phase precipitation and grain refinement in the Al-Mg-Si alloy rod are accelerated, thus optimizing the mechanical properties of the Al-Mg-Si alloy rod.
[0044] (II) Beneficial technical effects
[0045] First, compared with the prior art, the present invention provides a thermal aging treatment method for high-performance aluminum-magnesium-silicon alloy by ultrasonic vibration with short aging time and ultrasonic coupling. The beneficial technical effect is: by combining ultrasonic mechanical vibration with thermal aging treatment, the present invention can significantly improve the strength and hardness of the aluminum-magnesium-silicon alloy, realize the optimization of microstructures such as grain refinement, dislocation density regulation and strengthening phase precipitation, and achieve ideal comprehensive performance in a relatively short time.
[0046] Specifically, the aging time is significantly shortened from the conventional more than ten hours to 1-3 hours, which greatly improves the processing efficiency.
[0047] Specifically, the mechanical properties are significantly improved, and the tensile strength and hardness are significantly improved, with a higher strengthening effect. Through ultrasonic vibration treatment, the tensile strength and hardness of aluminum-magnesium-silicon alloy are greatly improved, the hardness can reach 120-125HV, and the tensile strength is increased to 320-330MPa. The overall performance of the material is significantly better than conventional treatment methods.
[0048] Specifically, effective regulation of grain refinement and dislocation density significantly enhanced the microstructural stability and homogeneity of aluminum-magnesium-silicon alloys. Optimal experiments showed that after 3 hours of ultrasonic vibration treatment, the tensile strength could reach 334MPa, which was more than 12.8% higher than conventional aging treatment. During ultrasonic vibration aging, high-frequency mechanical vibrations stimulated the recrystallization and rotation of the grains, resulting in a significant reduction in the size of the grains. After 3 hours of treatment at 150°C, the average grain size can be reduced from 10.24μm in the solid solution state to 6.5-7.0μm.
[0049] Secondly, compared with the prior art, the present invention provides a high-performance aluminum-magnesium-silicon alloy material with short-term ultrasonic coupling, and the beneficial technical effects are: the present invention provides a high-performance aluminum-magnesium-silicon alloy material with short-term ultrasonic coupling, with a hardness of 120-125HV, a tensile strength of 320-330MPa, a grain size of 10.24μm refined to 6.5-7.0μm, and a uniform distribution of the precipitated phase β" phase, which inhibits the transformation of the β" phase to the β' phase and the β phase; and ultrasonic vibration excites the proliferation and movement of dislocations, so that the dislocations in the matrix are evenly distributed to avoid stress concentration. In addition, ultrasonic vibration repairs surface microscopic defects to make the surface of the aluminum-magnesium-silicon alloy material smoother. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The dislocation distribution of the aluminum-magnesium-silicon alloy sample of the ultrasonically coupled short-ageing high-performance aluminum-magnesium-silicon alloy material under different heat treatment methods described in the present invention is measured;
[0051] Figure 2 The determination of the precipitation of strengthening phases in the aluminum-magnesium-silicon alloy sample under different heat treatment times and conditions in the transmission electron microscope (TEM) image of the ultrasonically coupled short-aging high-performance aluminum-magnesium-silicon alloy material of the present invention;
[0052] Figure 3 The ultrasonically coupled short-ageing high-performance aluminum-magnesium-silicon alloy material of the present invention is used to measure the hardness of aluminum-magnesium-silicon alloy rod samples in different heat treatment methods;
[0053] Figure 4 The present invention provides a method for measuring the grain morphology and grain size of the high-performance aluminum-magnesium-silicon alloy with short-term aging and ultrasonic coupling under different treatment conditions.
[0054] Figure 5 The tensile strength of the high-performance aluminum-magnesium-silicon alloy with short-term ultrasonic coupling is measured by different heat treatment methods;
[0055] Figure 6 The results of the hardness comparison of the ultrasonically coupled short-aging high-performance aluminum-magnesium-silicon alloy material at different ultrasonic vibration aging temperatures described in the present invention;
[0056] Figure 7 The preparation flow chart of the ultrasonically coupled short-aging high-performance aluminum-magnesium-silicon alloy and the ultrasonic vibration thermal aging treatment method of the present invention;
[0057] Figure 8 This is a schematic diagram of the overall structure of a laboratory of an ultrasonic aging vibration device according to the present invention;
[0058] Fig. 9This is a schematic diagram of the structure of the middle transducer and the horn in the laboratory of the ultrasonic aging vibration device of the present invention;
[0059] Fig.10 This is a schematic diagram of the component structure in a laboratory of an ultrasonic aging vibration device according to the present invention;
[0060] Fig.11 This is a schematic diagram of ultrasonic vibration heat aging treatment performed in a laboratory using an ultrasonic aging vibration device according to the present invention.
[0061] Reference numerals: ultrasonic generator 1; transducer 2; horn 3; drying box 4; fixed base 5; fixed frame 6. DETAILED DESCRIPTION
[0062] The ultrasonic vibration thermal aging treatment method and high-performance aluminum-magnesium-silicon alloy material described in the present invention break the traditional barrier that dislocations can only be generated by plastic deformation through the coupling of ultrasonic mechanical vibration and temperature field, can regulate the dislocation density in a short time, significantly improve the comprehensive performance of the aluminum-magnesium-silicon alloy material, optimize the microstructure of the new aluminum-magnesium-silicon alloy material, and provide innovative ideas for the heat treatment method for strengthening the mechanical properties of the new aluminum-magnesium-silicon alloy material.
[0063] The ultrasonic vibration heat aging treatment method and high-performance aluminum-magnesium-silicon alloy material described in the present invention need to go through four stages: solution treatment, water cooling quenching, ultrasonic mechanical vibration heat aging treatment and microstructure measurement. The specific purposes of the four stages are as follows:
[0064] The first stage (pretreatment 1): solution treatment, the purpose of which is to fully dissolve the coarse second phase in the rod-shaped aluminum-magnesium-silicon alloy matrix through high temperature to form a supersaturated solid solution, ensuring that the rod-shaped aluminum-magnesium-silicon alloy material obtains the best performance in the subsequent quenching and aging process;
[0065] The second stage (pretreatment 2): water cooling quenching, the purpose is to prevent the formation of precipitation phase through rapid cooling, maintain the rod-shaped aluminum-magnesium-silicon alloy material in a highly solid solution state after solution treatment, thereby ensuring the effect of subsequent aging treatment;
[0066] The third stage: thermal aging treatment of ultrasonic mechanical vibration, which is subdivided into the period of introducing ultrasonic mechanical vibration and heating treatment, thermal aging treatment period, and short-time coupling treatment;
[0067] The purpose of the heating treatment period is to introduce ultrasonic mechanical vibration during the heating process of 1-3 hours at 130°C-200°C to form a coupled field of temperature + mechanical vibration, regulate the generation and movement of dislocations, and further improve the microstructural properties of the rod-shaped aluminum-magnesium-silicon alloy material;
[0068] The purpose of the heat aging treatment period is to promote the maximum precipitation of the β" strengthening phase through heat aging treatment at 130°C-200°C for 1-3 hours, and at the same time, to optimize the microstructure by regulating the dislocation density by combining ultrasonic mechanical vibration, thereby improving the mechanical properties of the rod-shaped aluminum-magnesium-silicon alloy material;
[0069] The purpose of the short-time coupling treatment is to complete the regulation of dislocation density and optimize the microstructure to improve the overall performance of the rod-shaped aluminum-magnesium-silicon alloy material through a short-time coupling treatment of 1-3 hours at 130°C-200°C under the action of temperature and ultrasonic mechanical vibration;
[0070] The fourth stage (post-treatment): microstructure measurement, the purpose of which is to observe the dislocation density and microstructure of the rod-shaped aluminum-magnesium-silicon alloy material sample after treatment through a transmission electron microscope (TEM), and to measure the microstructure changes of the rod-shaped aluminum-magnesium-silicon alloy material after treatment.
[0071] like Figure 7 As shown, the ultrasonic vibration heat aging treatment method and high-performance aluminum-magnesium-silicon alloy material described in the present invention are specifically prepared as follows:
[0072] The first stage (pre-treatment 1): solution treatment
[0073] S1. Aluminum material preparation and pretreatment: Select hot extruded aluminum-magnesium-silicon alloy rods with a length of 25 cm and a diameter of 12 mm. Ensure that the surface of the aluminum-magnesium-silicon alloy rods is clean and free of oil, oxide layer or impurities, so as not to affect heat conduction and dissolution efficiency during solution treatment.
[0074] S2. Tube furnace settings: Use a tube furnace for solution treatment; check the temperature uniformity of the tube furnace in advance to ensure consistent heating effect in each area; preheat to 555℃, confirm that the tube furnace is always maintained at 555℃ to avoid excessive temperature fluctuations, ensure stable air flow or other heating media in the furnace, avoid local grain coarsening due to excessively high temperature, and prevent the second phase from being fully dissolved due to too low temperature, which affects the effect of subsequent quenching and aging processes;
[0075] S3. Start of solution treatment: When the furnace temperature reaches 555°C stably, the aluminum-magnesium-silicon alloy rods prepared in S1. are quickly placed in the tubular furnace; the aluminum-magnesium-silicon alloy rods must be located in the center of the furnace chamber to ensure that the aluminum-magnesium-silicon alloy rods are evenly heated and avoid direct contact with the furnace wall, which may cause local overheating; the aluminum-magnesium-silicon alloy rods are in a stable position throughout the heating process and avoid local temperature differences caused by external factors such as airflow in the furnace;
[0076] S4. Solution treatment and heat preservation: The aluminum-magnesium-silicon alloy rods in the tube furnace need to be kept at 555°C for 1 hour to ensure that all coarse second phases in the alloy matrix are fully dissolved; during the heat preservation period, the second phases in the aluminum-magnesium-silicon alloy (such as Mg2Si, AlFeMnSi) will be fully dissolved into the alloy matrix to form a uniform supersaturated solid solution; 1 hour of heat preservation is the key to solution treatment. If the time is too short, the second phase in the aluminum-magnesium-silicon alloy will not be fully dissolved, while if the time is too long, the grain growth of the aluminum-magnesium-silicon alloy matrix may be caused, affecting the final mechanical properties of the aluminum-magnesium-silicon alloy rods;
[0077] Through the solution treatment stage, it can be ensured that the coarse second phase in the aluminum-magnesium-silicon alloy rod is fully dissolved to form a supersaturated solid solution, laying the foundation for subsequent quenching and aging treatment.
[0078] The second stage (pre-treatment 2): water cooling quenching
[0079] S1. Cooling pretreatment: After the solution treatment, the aluminum alloy should be quenched immediately to avoid precipitation of strengthening phase at high temperature, which will affect the subsequent aging effect. First, prepare a water-cooled quenching tank. When the solution treatment is about to be completed, a large enough quenching tank should be prepared in advance to ensure that there is enough water in the tank to completely cover the aluminum-magnesium-silicon alloy rod to avoid uneven local cooling.
[0080] S2. Adjust the water temperature: control the water temperature in the quenching tank at about 20°C. If the water temperature is too high, it will affect the cooling rate. If the water temperature is too low, it will cause excessive quenching stress and cracks. Then prepare a stirring device. You can use a slight water flow stirring device or manually stir the water in the water tank to keep the water flowing evenly to avoid local hot water accumulation and uneven cooling. The water temperature is controlled at about 20°C throughout the process to ensure a moderate cooling rate. Although too low a water temperature speeds up cooling, it is easy to cause excessive quenching stress and even cracks.
[0081] S3. Quenching operation: After the solution treatment is completed, the heated aluminum-magnesium-silicon alloy rods are quickly taken out from the tube furnace to avoid oxidation caused by excessive surface temperature of the aluminum-magnesium-silicon alloy rods and reduce the exposure time of the rods in the air; the aluminum-magnesium-silicon alloy rods at high temperature are immediately placed vertically into the water-cooled quenching tank to ensure that the entire surface of the aluminum-magnesium-silicon alloy rods is evenly in contact with water for cooling; the rods should be inserted vertically into the water to avoid direct impact on the bottom of the quenching tank or other hard objects during the quenching process to prevent deformation, warping or surface damage of the rods due to uneven quenching process;
[0082] S4. Uniform cooling: The entire aluminum-magnesium-silicon alloy bar needs to be fully cooled to room temperature (about 20°C) in water and kept in water for at least 10-20 minutes; during the cooling process, the aluminum-magnesium-silicon alloy bar needs to be slightly shaken or the water tank needs to be stirred by water flow to ensure that the internal and external temperatures are evenly reduced to the water temperature to avoid local heat accumulation affecting the quenching effect of the aluminum-magnesium-silicon alloy bar; after the aluminum-magnesium-silicon alloy bar is completely cooled, the bar is slowly taken out of the water-cooled quenching tank; during the cooling process, the material should be prevented from being rapidly cooled unevenly, especially when placed and operated in the water tank, and the aluminum-magnesium-silicon alloy bar should be kept from being subjected to external forces during the quenching process to avoid deformation;
[0083] S5. Take out and inspect: Check the surface of the aluminum-magnesium-silicon alloy rod for quenching cracks, deformation or other surface defects to ensure that the aluminum-magnesium-silicon alloy rod is intact.
[0084] Through the water-cooling quenching stage, the aluminum-magnesium-silicon alloy rod can maintain a high degree of solid solution state during the quenching process, laying a good foundation for subsequent heat treatment methods and mechanical property optimization.
[0085] The third stage: thermal aging treatment with ultrasonic mechanical vibration
[0086] Period 1: Introduction of ultrasonic mechanical vibration and heating treatment
[0087] S1. Tapping treatment: Select an aluminum-magnesium-silicon alloy rod that has been water-cooled and quenched, with a length of 25 cm, a diameter of 12 mm, and one end is tapped with a thread pitch of 1.75 mm; the purpose of tapping is to ensure that the ultrasonic transducer 2 can be firmly connected to the aluminum-magnesium-silicon alloy rod and the vibration is evenly transmitted;
[0088] S2. Surface cleaning: Ensure that the surface of the aluminum-magnesium-silicon alloy rod is clean and free of oxides or dirt to ensure a stable connection of the ultrasonic transducer 2 and uniform transmission of ultrasonic vibration;
[0089] S3. Prepare ultrasonic equipment: first select ultrasonic generator 1 with a power of 100W and a vibration frequency of 20kHz, and check the status of ultrasonic generator 1 to ensure that the power and frequency settings meet the requirements and can operate normally; then select ultrasonic transducer 2 and connect ultrasonic transducer 2 to ultrasonic generator 1; the vibration frequency of ultrasonic transducer 2 should be 20kHz, and the diameter of the bottom threaded hole should be 12mm. Ensure that transducer 2 is intact and the vibration frequency is consistent; before the thermal aging treatment operation, check the connection of all cables and interfaces to ensure that there is no looseness, all parts of the equipment are operating normally, and the vibration signal is transmitted correctly;
[0090] S4. Preparation for heating treatment: preheat the drying oven 4 to 150°C in advance to ensure that the temperature inside the drying oven 4 is uniform and stable and reaches the specified heating environment. Sufficient space should be reserved in the drying oven 4 to avoid direct contact between the aluminum-magnesium-silicon alloy rod and the oven wall to ensure uniform heat conduction;
[0091] S5. Install, fix and connect the equipment: install a fixed base 5 in the drying oven 4 to support and fix the other end of the aluminum alloy rod, ensure that the entire aluminum-magnesium-silicon alloy rod remains stable during the heating process, and ensure that the vibration is evenly transmitted; then connect the ultrasonic transducer 2 to the aluminum-magnesium-silicon alloy rod, and one end of the aluminum-magnesium-silicon alloy rod is tightly connected to the ultrasonic transducer 2 through the tapping end (thread pitch 1.75mm). When connecting, ensure that the threads are tightly matched and the contact between the transducer 2 and the aluminum-magnesium-silicon alloy rod is not loose, so as to ensure that the ultrasonic vibration can be evenly transmitted to the aluminum-magnesium-silicon alloy rod; proceed And fix the rod, insert the other end of the aluminum-magnesium-silicon alloy rod into the fixed base 5 in the drying box 4, the fixed base 5 ensures stability and allows the aluminum-magnesium-silicon alloy rod to maintain uniform force during the vibration process, avoiding the rod from deflecting or shaking; finally, adjust the position of the transducer 2, fix the ultrasonic transducer 2 outside the drying box 4, and ensure that the exhaust hole on the top of the drying box 4 is open, so that the ultrasonic vibration can be directly transmitted to the aluminum-magnesium-silicon alloy rod through the tapping end, and the connection between the transducer 2 and the aluminum-magnesium-silicon alloy rod should be located directly above the exhaust hole to ensure that the vibration transmission path is smooth and the operation is stable during the ultrasonic vibration and heating treatment process;
[0092] S6. Synchronous operation of heating in drying oven 4 and introducing ultrasonic vibration: During the heating process in drying oven 4, the aluminum-magnesium-silicon alloy rod is heated and vibrated synchronously at 150°C and 20kHz ultrasonic vibration is maintained, and the temperature control is used to promote the precipitation of the strengthening phase, and the ultrasonic vibration is combined to achieve the control of dislocation; at the same time, the ultrasonic generator 1 is started, and the aluminum alloy rod is mechanically vibrated at a frequency of 20kHz to ensure that the vibration is evenly transmitted to each part of the aluminum-magnesium-silicon alloy rod. At this time, the high-frequency vibration will produce a microscopic mechanical effect, which promotes the generation, movement and redistribution of dislocations; the time for simultaneous heating and ultrasonic vibration treatment is generally 1-3 hours, which can ensure that the aluminum-magnesium-silicon alloy rod completes the maximum precipitation of the strengthening phase in a short time, and the dislocation is regulated by mechanical vibration;
[0093] S7. Natural cooling: turn off the ultrasonic generator 1 and take out the aluminum alloy rod, and wait for natural cooling; at this time, the dislocation density of the aluminum-magnesium-silicon alloy rod will be effectively controlled.
[0094] Period 2: Heat aging treatment
[0095] S1. Preparation for aging treatment: Use an aluminum-magnesium-silicon alloy rod that has completed water-cooling quenching and is connected to an ultrasonic transducer 2; then set up a drying oven 4, preheat the drying oven 4 to 150°C in advance, ensure that the temperature in the drying oven 4 is evenly distributed, and avoid local overheating or overcooling; then check the ultrasonic generator 1 and the transducer 2 to ensure that the ultrasonic mechanical vibration equipment with a power of 100W and a frequency of 20kHz is ready, and the vibration transmission path is unobstructed; combine the thermal aging at 150°C with the 20kHz ultrasonic vibration to form a stable coupling field, ensuring that the aluminum-magnesium-silicon alloy rod completes dislocation regulation and strengthening phase precipitation in a short time;
[0096] S2. Aging treatment: put the aluminum-magnesium-silicon alloy rod into the drying oven 4, ensure that one end of the rod is connected to the fixed base 5 in the drying oven 4, and the other end is tightly connected to the external ultrasonic transducer 2 through the tapping end, ensure that the entire aluminum-magnesium-silicon alloy rod is stable and does not shake during the heating process and achieves uniform vibration;
[0097] S3. Insulation treatment: The temperature inside the drying oven 4 is kept constant at 150°C for aging insulation treatment; this temperature can effectively promote the precipitation of the β" phase and reduce the transformation of the β" phase to the β′ phase or the β phase, so as to achieve the maximum strengthening effect; according to the experimental requirements, the heating time is controlled within 1-3 hours to ensure that the β" strengthening phase is fully precipitated and the dislocation density reaches the ideal microstructural adjustment;
[0098] S4. Introducing synchronous ultrasonic vibration: During the heating aging process at 150°C, start the ultrasonic generator 1 and start introducing ultrasonic mechanical vibration with a frequency of 20kHz to ensure that the ultrasonic transducer 2 evenly transmits the vibration to the aluminum-magnesium-silicon alloy rod; then through the coupling effect of ultrasonic mechanical vibration and temperature field, the vibration will accelerate the generation and movement of dislocations, and promote the interaction between dislocations and strengthening phases to achieve the best; the acoustic vibration and heating process should be carried out simultaneously for 1-3 hours, and the vibration amplitude should be kept uniform to ensure that the entire aluminum-magnesium-silicon alloy rod is subjected to uniform force. The short aging treatment of 1-3 hours can effectively improve the performance of the aluminum-magnesium-silicon alloy rod and avoid excessive conversion of the β" phase into the β′ or β phase;
[0099] S5. Coupling field formation: First, a coupling effect is formed. Under the joint action of thermal aging treatment and ultrasonic mechanical vibration, a temperature + mechanical vibration coupling field is formed. This coupling field can promote the generation and redistribution of dislocations and optimize the dislocation density to the greatest extent. Then, dislocation regulation is formed. High-frequency mechanical vibration promotes the rapid generation and movement of dislocations in the microstructure to prevent excessive accumulation of dislocations and cause stress concentration. As time goes by, the precipitation of β" phase gradually stabilizes, and the dislocation density also reaches the optimal state with the balance process of temperature and vibration. Finally, the strengthening phase precipitates. Under the action of the coupling field, the precipitation of β" phase in the aluminum-magnesium-silicon alloy rod is retained to the greatest extent. Due to the relatively low aging temperature (150℃), the rate of conversion to β′ phase or β phase is significantly reduced, so that the β" phase can be fully precipitated, providing the best strengthening effect.
[0100] S6. Thermal aging treatment monitoring: On the one hand, pay attention to temperature monitoring, regularly check the temperature in the drying oven 4 to ensure a constant temperature environment of 150°C, and temperature fluctuations will affect the precipitation rate of the strengthening phase and the movement behavior of dislocations, so it is necessary to monitor the temperature stability in real time; on the other hand, pay attention to vibration monitoring, and regularly check the operating status of the ultrasonic transducer 2 through the display interface of the ultrasonic equipment or an external measuring device to ensure that the ultrasonic vibration with a frequency of 20kHz is always evenly transmitted to the aluminum-magnesium-silicon alloy rod to avoid uneven dislocation distribution caused by unstable vibration;
[0101] S7. Cooling: After the heat aging treatment and ultrasonic mechanical vibration are completed, the ultrasonic generator 1 and the drying oven 4 are turned off, the temperature is gradually reduced and the vibration is stopped; then the aluminum-magnesium-silicon alloy rod is taken out and placed at room temperature to cool naturally to avoid stress concentration caused by rapid cooling or material cracking of the aluminum-magnesium-silicon alloy rod;
[0102] Through heat aging treatment, the dislocation density and strengthening phase precipitation of Al-Mg-Si alloy rods will be precisely controlled, thereby significantly improving the mechanical properties of the material, such as strength, hardness and fatigue resistance.
[0103] Period 3: Short-term coupling processing
[0104] S1. Control the coupling treatment time: According to the final application requirements of the aluminum-magnesium-silicon alloy rod, the time of the coupling field treatment is controlled to be between 1 and 3 hours. Short-term treatment helps prevent excessive increase in dislocation density and ensures the precipitation of strengthening phases. The treatment time should be adjusted according to the final application requirements of the aluminum-magnesium-silicon alloy rod and maintained between 1 and 3 hours. Too long or too short a time will affect the effect of dislocation density and precipitation of strengthening phases. The specific choice of treatment time:
[0105] 1) 1 hour treatment: suitable for aluminum-magnesium-silicon alloy bars with high requirements for dislocation density and low requirements for strengthening phase precipitation; the 1-hour treatment effect is suitable for applications where medium requirements are required for measuring bar strength and hardness;
[0106] 2) 2-hour treatment: taking into account both dislocation density control and strengthening phase precipitation effect; the 2-hour treatment effect is suitable for the determination of aluminum-magnesium-silicon alloy bars that require higher strength and fatigue resistance;
[0107] 3) 3-hour treatment: suitable for materials that require higher dislocation density and more precipitation of strengthening phases; the 3-hour treatment effect is suitable for application scenarios where high strength, high temperature resistance or high fatigue resistance are measured, but too long a treatment time can easily lead to excessive dislocation accumulation and reduce the plasticity of the aluminum-magnesium-silicon alloy bar;
[0108] S2. Vibration frequency and intensity control: The vibration frequency of the ultrasonic generator 1 is set to 20kHz, which can effectively promote the generation and movement of dislocations, and is conducive to the precipitation of strengthening phases and the interaction of dislocations; the vibration frequency of 20kHz should act evenly on the rod, and the vibration intensity can be evenly distributed on the entire aluminum-magnesium-silicon alloy rod to avoid excessive or weak local vibration, ensuring uniform distribution of dislocations and precipitation of strengthening phases; excessive vibration will cause local stress concentration in the material and affect the uniform distribution of dislocations, while insufficient vibration may reduce the efficiency of dislocation movement; during the short-term coupling process, it is necessary to regularly monitor the status of the ultrasonic generator 1 and the transducer 2 to ensure that the vibration intensity remains stable within the set range;
[0109] S3. Natural cooling: When the ultrasonic mechanical vibration and temperature coupling treatment time reaches 1-3 hours, first turn off the ultrasonic generator 1, stop the vibration, and at the same time turn off the heating system of the drying box 4, gradually reduce the temperature, and avoid stress concentration and material damage caused by rapid cooling; then take the aluminum-magnesium-silicon alloy rod out of the drying box 4 and the fixture, and place it at room temperature for natural cooling. The natural cooling lasts for 1-2 hours to ensure that the surface and interior of the rod are evenly cooled to room temperature to avoid residual stress in the aluminum-magnesium-silicon alloy rod. Natural cooling can avoid excessive stress concentration in the aluminum-magnesium-silicon alloy rod caused by rapid cooling, and prevent cracks or deformation. After cooling is completed, conduct a preliminary inspection of the surface of the aluminum-magnesium-silicon alloy rod to ensure that there are no cracks, deformation or other surface defects during the cooling process.
[0110] Through short-time coupling treatment, the dislocation density of Al-Mg-Si alloy rods is effectively controlled, and the β" phase is precipitated to the maximum extent, which provides a basis for improving the mechanical properties of Al-Mg-Si alloy rods.
[0111] Stage 4 (Post-processing): Microstructure determination
[0112] S1. Sampling: Ensure that the sampling area can represent the microstructure of the entire bar. First, select the samples of the aluminum-magnesium-silicon alloy bar. Sampling is performed from the aluminum-magnesium-silicon alloy bar after ultrasonic mechanical vibration and thermal aging treatment. Sampling is performed at different positions of the bar (such as the surface and the center area). Ensure that the analyzed aluminum-magnesium-silicon alloy bar samples can fully reflect the microstructural differences inside and outside the bar. When sampling, ensure that the aluminum-magnesium-silicon alloy bar size is a thin slice with a diameter of 3 mm, which can reflect the overall microstructural changes of the material. The aluminum-magnesium-silicon alloy bar sample is suitable for subsequent TEM microscopic observation; mechanically grind the sample to further reduce the thickness to a thickness range that can be electrolytic double sprayed (generally less than 0.1 mm);
[0113] S2. Electrolytic double spraying: Electrolytic double spraying is first performed. In order to obtain the thin film sample required for transmission electron microscopy, the aluminum alloy thin sheet is polished to a nanometer thickness (about 100nm) using an electrolytic double spraying device. The specific operation is as follows:
[0114] 1) Select appropriate electrolyte (such as 30% nitric acid-70% methanol solution) and control the nozzle pressure to make the aluminum-magnesium-silicon alloy rod sample thinner evenly during the electrolysis process; during the electrolysis process, the temperature should be controlled at about -20°C to avoid deformation or oxidation of the aluminum-magnesium-silicon alloy rod sample;
[0115] 2) Cleaning of rod samples: After electrolysis is completed, rinse the aluminum-magnesium-silicon alloy rod samples with deionized water or ethanol to prevent residues from affecting the observation effect;
[0116] 3) Rod sample drying: Place the cleaned samples in a clean environment to dry naturally, ensuring that the aluminum-magnesium-silicon alloy rod samples are free of moisture or residual solution to ensure clear imaging during TEM observation.
[0117] S3.TEM microstructure observation: Use a high-resolution transmission electron microscope (TEM) and adjust the acceleration voltage (generally 200kV-300kV) to obtain clear images of the Al-Mg-Si alloy rod sample with dislocations and strengthening phase precipitation;
[0118] 1) Observation of dislocation density: observe the distribution and density of dislocations in the treated aluminum-magnesium-silicon alloy rod samples, record the generation, movement and entanglement of dislocations at different positions, and the dislocation density can be estimated by the number of dislocations in a specific area under TEM, and analyze the changes in dislocation density under different treatment times;
[0119] 2) Observation of β" phase precipitation: Focus on observing the precipitation of β" strengthening phase, and analyze its precipitation quantity, size and distribution; β" phase is the key phase for strengthening Al-Mg-Si alloy rods. Nano-scale precipitates can be observed through TEM, so as to observe whether the β" phase is evenly distributed at the grain boundary and in the grain, and whether the morphology of the Al-Mg-Si alloy rod sample is uniform, so as to determine the heat treatment effect.
[0120] S4.TEM related results analysis: Through microstructural observation and research on the microstructural changes of the treated Al-Mg-Si alloy rod samples, the optimal coupling field treatment time and parameters can be further determined, thereby improving the performance of the Al-Mg-Si alloy rod samples;
[0121] 1) Analysis of the relationship between dislocation density and mechanical properties: By comparing the changes in dislocation density under different coupling treatment times, the effect of dislocation density on the strength and toughness of Al-Mg-Si alloy bars is analyzed; an appropriate amount of dislocation density helps to improve the strength of Al-Mg-Si alloy bar samples, but too high a dislocation density may lead to increased brittleness;
[0122] 2) β" phase precipitation and strengthening effect: By analyzing the precipitation state of β" phase, the effect of strengthening on the strength and hardness of Al-Mg-Si alloy rods is analyzed; the size and uniformity of β" phase will directly affect the comprehensive mechanical properties of Al-Mg-Si alloy rod samples;
[0123] 3) Microstructural change trend: The microstructure of the Al-Mg-Si alloy rod sample was observed by TEM, and the change patterns of dislocation density and strengthening phase precipitation with treatment time during the coupling field treatment were summarized.
[0124] Furthermore, the ultrasonic vibration heat aging treatment method and high-performance aluminum-magnesium-silicon alloy material described in the present invention include the following mechanisms:
[0125] First, the mechanism of the ultrasonic vibration aging in the present invention to promote the precipitation of the strengthening phase is: in the temperature field, various atoms move randomly under the action of heat, but if the aging temperature is low, the atomic movement is relatively slow, and the probability of meeting and combining into a phase is small. Under low-temperature aging, the introduction of ultrasonic mechanical vibration has a high mechanical vibration frequency, which can be used as energy to promote the movement of atoms and combine into a phase, so the precipitation rate of the strengthening phase will be accelerated.
[0126] Specifically, from the relationship between atomic movement and thermal field, the increase in temperature allows the atoms in the aluminum-magnesium-silicon alloy rod to gain energy, forming a thermal energy effect, and then to move randomly. This irregular movement is the basis of atomic diffusion; in the solid solution, atoms achieve relative movement through vibration and jumping. The increase in random movement leads to more opportunities for encounter and combination, forming a diffusion mechanism. Specifically, in terms of the limitations of low-temperature aging, at a lower aging temperature (such as 150°C), the movement of atoms is slower, resulting in insufficient ability of the aluminum-magnesium-silicon alloy rod to move in the lattice, affecting the movement rate; due to insufficient energy, it is difficult for atoms to reach the critical state required for combination, and the probability of combination is low, resulting in a slow precipitation rate of the strengthening phase (such as β" phase).
[0127] Specifically, from the introduction of ultrasonic mechanical vibration, ultrasonic vibration provides high-frequency mechanical energy, which stimulates the atomic energy in the aluminum alloy and significantly increases its movement rate; the additional energy breaks the static state of the atoms, making them more active at the vibration frequency, and the dynamic enhancement prompts the atoms to move to a higher energy state. Specifically, from the perspective of increasing the probability of bonding, as the speed of atomic movement increases, the frequency of movement increases, and the frequency of movement of the aluminum-magnesium-silicon alloy rod in the lattice also increases; the rapid movement makes it easier for atoms to meet, enhancing the chance of bonding, and significantly increasing the probability of bonding to form a strengthened phase. Specifically, from the formation of the coupling field, the combined action of ultrasonic vibration and temperature forms a coupling field, which can effectively enhance the generation and movement of dislocations; ultrasonic vibration changes the movement mode of atoms, making it easier to bond and precipitate phases under different energy states. Specifically, from the precipitation of the strengthening phase, the precipitation rate of the strengthening phase (such as β" phase) is significantly accelerated under the promotion of ultrasonic vibration; and the acceleration effect enables the strengthening phase to reach the required precipitation amount within a shorter aging time and maintain its uniform distribution. In summary, by introducing ultrasonic vibration, the atomic movement ability of the aluminum alloy is effectively improved, the probability of bonding is increased, and the precipitation of the strengthening phase is promoted. The method combines the advantages of low-temperature aging and avoids the grain coarsening caused by high-temperature treatment. Finally, the microstructure of the aluminum-magnesium-silicon alloy is optimized and its mechanical properties are improved.
[0128] Second, the mechanism of ultrasonic vibration aging increasing dislocation density: in the coupled experiment of temperature and ultrasonic mechanical vibration, dislocations evolve in the form of continuous combination-cancellation. Since aging and ultrasonic mechanical vibration are carried out simultaneously, in the experiment of ultrasonic vibration aging for 1 hour, under the influence of mechanical vibration, the exciting stress generated by ultrasonic vibration will first provide driving force for the grains, causing them to slide or climb from high energy to lower energy, leaving dislocations at the original positions. Therefore, dislocations begin to proliferate and move in large numbers, forming a large number of dislocation tangles. However, the energy provided by strong mechanical vibration will cause the already formed tangles to decompose into dislocation lines again. When these dissolved dislocation lines meet other dislocations, some will combine again to form tangles, and some will cancel each other out in opposite directions. In addition, vacancies move violently under the insulation state. When these vacancies gather on dislocation tangles, they will dissolve into dislocation lines. However, the experimental time is only 1 hour, and the newly generated dislocation tangles are much more than the dissolved ones. Therefore, most of the observed ones are dislocation tangles. However, as the experimental time increases, in the ultrasonic vibration aging experiments of 2h and 3h, due to the long period of mechanical vibration, most of the grains have moved to a stable and appropriate position. Although mechanical vibration can still cause dislocations to increase and move, the experimental time is long, and therefore more dislocations are dissolved and annihilated. Therefore, a small amount of dislocation entanglement and more dislocation lines are observed in the matrix, but in general, the dislocation density is higher than that in the solid solution state.
[0129] Third, the mechanism of ultrasonic vibration aging grain refinement: first, ultrasonic vibration causes the dislocation density to increase, while vacancy diffusion leads to dislocation climb and offsets vacancies and atomic dislocation to form new grain boundaries, resulting in grain refinement. In addition, ultrasonic vibration produces dislocation proliferation, and dislocation climb caused by vacancy movement divides the elongated grains formed by extrusion into dislocation cells along the length direction. As the ultrasonic excitation stress continues, dislocation movement further adjusts the crystallographic orientation of the subgrains. This process is repeated and promotes grain refinement. In addition, ultrasonic excitation stress will make The dislocation reaction at the grain boundary intensifies, and the vacancies left by the dislocation dissolution increase the distortion energy at the grain boundary. With the action of ultrasonic vibration and aging temperature, the atoms in the micro-area undergo recrystallization to achieve grain refinement. In addition, the exciting stress brought by the ultrasonic vibration causes the originally tightly arranged grains to loosen, causing the grains to climb or slide from high energy to low energy at the microscopic level. In this process, the loosened grains will be broken by the strong exciting stress and gradually become smaller grains. After that, these small grains will move to the appropriate position and arrange tightly again.
[0130] Specifically, from the perspective of increasing dislocation density, ultrasonic vibrations stimulate atoms in the aluminum-magnesium-silicon alloy, causing dislocations (linear defects inside the crystal) to be generated and increased; the increase in dislocation density means more crystal defects, which provides a basis for subsequent grain refinement; and dislocations interact in the crystal to form new defect structures, thereby promoting the evolution of the microstructure of the aluminum-magnesium-silicon alloy. Specifically, from the perspective of vacancy diffusion and dislocation movement, the stress excited by ultrasonic vibrations causes vacancies (point defects with missing atoms) to diffuse rapidly, and these vacancies provide a path for the movement of dislocations; when dislocations approach vacancies, the missing atomic positions in the crystal structure will offset each other, forming new grain boundaries, increasing the defect concentration inside the crystal, and this dynamic process accelerates grain refinement. Specifically, from the perspective of segmentation of slender grains, the proliferation of dislocations and the movement of vacancies cause the originally slender grains to be squeezed along the length direction, resulting in the missing atomic positions in the crystal structure being segmented into multiple dislocation cells (dislocation arrangements in local areas), and these newly formed grain boundaries create conditions for grain refinement. Specifically, from the perspective of adjusting the subgrain orientation, under the action of continuous ultrasonic excitation stress, the movement of dislocations continuously adjusts the crystallographic orientation of subgrains (small areas within grains), making the stress distribution inside the crystal more uniform. The uniform stress distribution helps to reduce the energy barrier of dislocation activity and promote grain refinement. Specifically, from the perspective of dislocation reaction and distortion energy increase, ultrasonic excitation stress accelerates the dislocation reaction near the grain boundary, leading to the annihilation of dislocations; when dislocations are annihilated, the vacancies left behind increase the distortion energy of the grain boundary, and the energy increase promotes the subsequent recrystallization process, making the formation of new grains more effective. Specifically, from the perspective of loosening and breaking of grains, the excitation stress caused by ultrasonic vibration causes the originally tightly arranged grains to loosen, prompting these grains to slide or climb from a high-energy state to a low-energy state; and the strong excitation stress will also break these loose grains into smaller sizes, thereby creating more opportunities for grain refinement. Specifically, from the rearrangement of small grains, the fine grains tend to move to positions with lower energy in the microscopic environment. After dynamic reorganization, the missing atomic positions in the crystal structure are rearranged into a more compact structure, ensuring the formation of refined grains, thereby optimizing the mechanical properties of the aluminum-magnesium-silicon alloy.
[0131] Furthermore, the ultrasonically coupled short-term high-performance aluminum-magnesium-silicon alloy material described in the present invention has the following characteristics:
[0132]
[0133]
[0134] The high-performance aluminum-magnesium-silicon alloy material with high performance and short aging time obtained by the present invention has a smoother surface, finer and evenly distributed grains, and significantly improved precipitate density after being treated with ultrasonic vibration aging at 150°C for 3 hours; the aluminum-magnesium-silicon alloy rod has a stable chemical composition, a large amount of β" phase precipitation and even distribution, and very few β' phases and β phases; the aluminum-magnesium-silicon alloy rod has significant grain refinement, a small and evenly distributed precipitate size, and greatly improved dislocation density.
[0135] In terms of performance, the high-performance aluminum-magnesium-silicon alloy material with high-performance ultrasonic coupling and short aging obtained by the present invention has greatly improved hardness and tensile strength, with hardness reaching 120-125HV and tensile strength reaching 320-330MPa, while maintaining good toughness and plasticity. Compared with conventional aging or higher temperature treatment (such as 170℃), ultrasonic vibration aging at 150℃ can achieve the best comprehensive mechanical properties.
[0136] Example 1 Specific example of ultrasonic vibration aging temperature of 150°C and ultrasonic vibration aging for 1h
[0137] In a specific embodiment, the hot extruded rod-shaped aluminum-magnesium-silicon alloy is subjected to a method step of solution treatment, rapid water cooling, and ultrasonic mechanical vibration combined with thermal aging.
[0138] First, place the rod-shaped aluminum-magnesium-silicon alloy in a tubular furnace and set the solid solution temperature to 555°C. After the furnace temperature rises to the target temperature, keep it for 1 hour for solid solution treatment. After the solid solution is completed, immediately take out the aluminum alloy rod and quickly cool it in water at about 20°C to ensure that it remains in a highly solid solution state.
[0139] Thermal aging is carried out in the drying oven 4, and the temperature is set to 150°C to reduce the transformation of the β" phase into the β' phase and the β phase, and to retain the precipitated β" strengthening phase to the greatest extent. During the thermal aging process, an ultrasonic vibration device (power 100W, frequency 20KHz) is used to apply ultrasonic mechanical vibration to the aluminum alloy. The ultrasonic transducer 2 is stably connected to the tapping end of the aluminum alloy through a threaded hole to ensure that the ultrasonic wave is evenly distributed throughout the aluminum-magnesium-silicon alloy rod. Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 1 hour. After completion, no additional thermal aging treatment is required.
[0140] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 150°C and ultrasonic vibration aging for 1h are as follows: in terms of morphology, the surface of the high-performance aluminum-magnesium-silicon alloy rod obtained is smooth, without obvious defects, and the grains are uniform. Small strengthening phase precipitates may appear and are evenly distributed; in terms of composition, the chemical composition of the high-performance aluminum-magnesium-silicon alloy rod obtained remains stable, and the precipitated phase is mainly β" phase to ensure the strengthening effect. A small amount of β′ phase and β phase may be observed; in terms of microstructure, the grain size is reduced through scanning electron microscopy (SEM) observation, and the precipitated phase of the high-performance aluminum-magnesium-silicon alloy rod is needle-shaped or flaky, which enhances the mechanical properties of the aluminum-magnesium-silicon alloy rod. Transmission electron microscopy (TEM) can be used to analyze the distribution and morphology of the precipitated phase, showing that the high-performance aluminum-magnesium-silicon alloy rod has higher strength and toughness.
[0141] Example 2 Specific example of ultrasonic vibration aging temperature of 150°C and ultrasonic vibration aging for 2h
[0142] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 2 hours. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0143] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 150°C and ultrasonic vibration aging for 2 hours are as follows: in terms of morphology, the surface of the high-performance aluminum-magnesium-silicon alloy rod obtained is smooth, the grains are more uniform, and the distribution of the strengthening phase precipitates is more dense and fine, which enhances the appearance quality of the high-performance aluminum-magnesium-silicon alloy rod obtained; in terms of composition, the chemical composition is still stable, the precipitation amount of the β" phase increases, and at the same time, less β' phase and β phase may appear, and the strengthening effect is more significant; in terms of microstructure, smaller grain size and more uniform distribution of precipitated phases are observed using SEM, and TEM analysis shows that the number of β" phases is significantly increased, which helps to improve the strength and toughness of the high-performance aluminum-magnesium-silicon alloy rod, making the material more advantageous in mechanical properties. Therefore, the high-performance aluminum-magnesium-silicon alloy material with high-performance ultrasonic coupling and short-aging and its enhanced heat treatment method described in the present invention further optimizes the microstructure and performance of the high-performance aluminum-magnesium-silicon alloy rod by ultrasonic vibration treatment for a longer time during the aging process.
[0144] Example 3 Specific example of ultrasonic vibration aging temperature of 150°C and ultrasonic vibration aging for 3 hours
[0145] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 3 hours. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0146] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 150°C and ultrasonic vibration aging for 2 hours are as follows: in terms of morphology, the surface of the aluminum-magnesium-silicon alloy rod is extremely smooth, the grains are finer and more uniform, the distribution density of the precipitated phase is significantly improved, and the appearance shows a higher processing quality; in terms of composition, the chemical composition remains stable, the precipitation amount of the β" phase is significantly increased, and the amount of the β′ phase and the β phase is small, which further enhances the strengthening effect of the aluminum-magnesium-silicon alloy rod; in terms of microstructure, SEM observed that the grain size is greatly reduced, the precipitated phase is more uniform and fine, and TEM analysis shows that the distribution of the β" phase is very uniform, which effectively improves the strength and toughness of the aluminum-magnesium-silicon alloy rod, making it more advantageous in mechanical properties. By extending the time of ultrasonic vibration aging, the comprehensive performance of the aluminum-magnesium-silicon alloy rod has been further optimized.
[0147] Comparative Example 1 Specific Example of 1 solid solution state
[0148] In a specific embodiment, the hot extruded rod-shaped aluminum-magnesium-silicon alloy is subjected to a method step of solution treatment, rapid water cooling, and ultrasonic mechanical vibration combined with thermal aging.
[0149] First, place the rod-shaped aluminum-magnesium-silicon alloy in a tubular furnace and set the solid solution temperature to 555°C. After the furnace temperature rises to the target temperature, keep it for 1 hour for solid solution treatment. After the solid solution is completed, immediately take out the aluminum alloy rod and quickly cool it in water at about 20°C to ensure that it remains in a highly solid solution state.
[0150] The solid solution aluminum-magnesium-silicon alloy rod obtained through the above steps has the following specific characteristics: the surface of the treated aluminum-magnesium-silicon alloy rod should be smooth and uniform without obvious oxide layer, cracks or bubbles, and rapid water cooling can prevent the surface from overheating and maintain a good appearance. The aluminum-magnesium-silicon alloy rod maintains its original geometric shape without bending or deformation, indicating that the heat treatment process is properly controlled.
[0151] Comparative Example 2 Specific Example of Ultrasonic Vibration Aging Temperature of 130°C and Ultrasonic Vibration Aging for 1h
[0152] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 1 hour. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0153] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 130°C and ultrasonic vibration aging for 1h are as follows: in terms of morphology, the grains are slightly refined, and the grain arrangement direction remains consistent with the extrusion direction; in terms of composition, the amount of β" phase precipitation is small, and the precipitation effect of the strengthening phase is not significant, but it is relatively stable and no transformation occurs; in terms of microstructure, the dislocation density and entanglement increase is limited, the residual stress is high, and the strengthening effect is weak. Finally, the hardness and tensile strength of the aluminum-magnesium-silicon alloy rod are slightly improved, but due to the low temperature limitation, the precipitation of the β" phase and the increase of the dislocation density are limited, so the comprehensive performance of the aluminum-magnesium-silicon alloy rod is improved to a small extent.
[0154] Comparative Example 3 Specific Example of Ultrasonic Vibration Aging Temperature of 130°C and Ultrasonic Vibration Aging for 2h
[0155] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 2 hours. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0156] The specific characterization of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 130°C for 2 hours is as follows: After ultrasonic vibration aging at 130°C for 2 hours, the morphology, composition and microstructure of the aluminum-magnesium-silicon alloy rod are optimized, but due to the low aging temperature, the strengthening effect is limited, which is manifested in grain refinement, gradual precipitation of β" phase and increased dislocation density. From the morphological point of view, the grains are further refined, the grains are arranged in order, and the orientation tends to be consistent. From the component point of view, the β" phase gradually precipitates, but the number and size are still small, and the strengthening effect gradually emerges. From a microscopic point of view, the dislocation density increases significantly, the strengthening phase is evenly distributed, and the dislocation entanglement phenomenon increases, which improves the mechanical properties of the aluminum-magnesium-silicon alloy rod. Finally, the obtained aluminum-magnesium-silicon alloy rod has improved hardness and tensile strength, but due to the low aging temperature, the strengthening effect is slightly weaker than that of aging at 150°C, which is suitable for application scenarios with low strengthening requirements.
[0157] Comparative Example 4 Specific Example of Ultrasonic Vibration Aging Temperature of 130°C and Ultrasonic Vibration Aging for 3h
[0158] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 3 hours. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0159] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 130°C and ultrasonic vibration aging for 3h are as follows: in terms of morphology, the grains are arranged in an orderly manner and the orientation tends to be consistent; in terms of composition, the amount of β" phase precipitation increases and exists stably, and the strengthening effect is significant; in terms of microscopic, the dislocation density is further improved, the dislocation entanglement phenomenon is obvious, the strengthening phase is evenly distributed, and the aluminum-magnesium-silicon alloy rod shows a good strengthening effect; in terms of performance, the hardness and tensile strength are significantly improved, the hardness reaches about 115HV, and the tensile strength is close to 290MPa. Although the strengthening effect at 130°C is not as obvious as that at 150°C or 170°C, the aluminum-magnesium-silicon alloy rod still shows good comprehensive performance through a longer period of ultrasonic vibration aging, and is suitable for applications requiring higher stability and good strength.
[0160] Comparative Example 5 Specific Example of Ultrasonic Vibration Aging Temperature of 170°C and Ultrasonic Vibration Aging for 1h
[0161] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 1 hour. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0162] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 170℃ and ultrasonic vibration aging for 1h are as follows: in terms of morphology, the grain size is reduced, but the refinement effect is limited, the banded structure of the grains still exists, and the overall organization arrangement has no obvious change; in terms of composition, a large amount of β" phase is precipitated, but some β" phases have begun to transform into β' phase or β phase, and the strengthening effect is slightly unstable at high temperature; in terms of microscopic, although the dislocation density has increased, due to the high temperature, the dislocation climb and annihilation are more, and the distribution of the strengthening phase of the aluminum-magnesium-silicon alloy rod is dense but not uniform; in terms of performance, the hardness and tensile strength of the aluminum-magnesium-silicon alloy rod are improved, but the improvement is limited, the hardness can reach 115-120HV, the tensile strength is about 300MPa, and the strengthening effect weakens with time. Compared with the treatment at 150℃, the aluminum-magnesium-silicon alloy rod can quickly improve the hardness and strength in a short time by ultrasonic vibration aging at 170℃, but the high temperature limits its long-term strengthening effect.
[0163] Comparative Example 6 Specific Example of Ultrasonic Vibration Aging Temperature of 170°C and Ultrasonic Vibration Aging for 2h
[0164] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 2 hours. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0165] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 170°C and ultrasonic vibration aging for 2h are as follows: in terms of morphology, the grain refinement effect is limited, the banded structure is maintained, and some grains show a growth trend at high temperature; in terms of composition, a large amount of β" phase precipitates quickly, but some β" phases gradually transform into β' phase or β phase, and the strengthening effect of the obtained aluminum-magnesium-silicon alloy rod is weak; in terms of microscopic, the dislocation density increases, and the dislocation entanglement phenomenon is significant, but the high temperature causes the annihilation of dislocations, and the strengthening phase distribution of the obtained aluminum-magnesium-silicon alloy rod is relatively uniform but fails to fully exert the maximum effect; in terms of performance, the hardness and tensile strength are significantly improved, the hardness is about 115-120HV, and the tensile strength is increased to 310-320MPa. However, due to the β" phase transformation and dislocation annihilation, the stability of the performance improvement of the obtained aluminum-magnesium-silicon alloy rod is weak. Compared with aging at 150℃, high-temperature treatment at 170℃ can quickly improve the performance, but long-term treatment will easily lead to a decrease in the transformation performance of the strengthening phase of the obtained aluminum-magnesium-silicon alloy rod.
[0166] Comparative Example 7 Specific Example of Ultrasonic Vibration Aging Temperature of 170°C and Ultrasonic Vibration Aging for 3h
[0167] Ultrasonic vibration and thermal aging are carried out simultaneously, and the time is set to 3 hours. After completion, no additional thermal aging treatment is required. The specific steps are the same as those in Example 1.
[0168] The specific characteristics of the aluminum-magnesium-silicon alloy rod obtained after ultrasonic vibration aging at a temperature of 170°C and ultrasonic vibration aging for 3 hours are as follows: in terms of morphology, the grain size is uneven, grain growth occurs in some areas, the banded structure is still obvious, and the grain refinement effect is limited; in terms of composition, a large amount of β" phase is precipitated in the obtained aluminum-magnesium-silicon alloy rod, but under high temperature and long-term conditions, part of the β" phase gradually transforms into β' phase and β phase, and the strengthening effect is weakened; in terms of microscopic, the dislocation density increases in the early stage, and there are many dislocation entanglements, but long-term high-temperature treatment leads to dislocation climb and annihilation, and the dislocation density decreases in the later stage, and the distribution of the strengthening phase of the obtained aluminum-magnesium-silicon alloy rod tends to be uneven, and the strengthening effect in some areas is weakened. In terms of material properties, the improvement effect of hardness and tensile strength is significant in the early stage, but with the extension of aging time, the strengthening effect tends to be stable or slightly decreased, the hardness is about 115HV, and the tensile strength is about 305-315MPa. Compared with shorter aging time (such as 1 hour or 2 hours), the aluminum-magnesium-silicon alloy rod obtained by 3 hours of treatment did not significantly improve the performance. On the contrary, the room for performance improvement was limited due to the transformation of the strengthening phase and the annihilation of dislocations.
[0169] In order to further determine the performance of the aluminum-magnesium-silicon alloy material after heat treatment, the high-performance ultrasonically coupled short-aging high-performance aluminum-magnesium-silicon alloy material prepared in the above embodiments (1-3) and comparative examples (1-7) was subjected to dislocation distribution measurement, strengthening phase precipitation measurement, aluminum-magnesium-silicon alloy material hardness measurement, grain morphology and grain size measurement, tensile strength measurement and hardness comparison measurement of the scanning electron microscope (SEM) image of the surface morphology of the high-performance aluminum-magnesium-silicon alloy material.
[0170] Determination 1 Determination of dislocation distribution of aluminum-magnesium-silicon alloy samples under different heat treatment methods
[0171] according to Figure 1 The dislocation distribution diagram of aluminum-magnesium-silicon alloy samples under different heat treatment methods can be used to analyze the effect of ultrasonic vibration aging treatment on the dislocation structure. By observing the dislocation evolution at different time points, it can be concluded that ultrasonic vibration aging significantly affects the generation, movement and entanglement of dislocations, thereby affecting the mechanical properties of aluminum-magnesium-silicon alloy samples.
[0172] like Figure 1 As shown in the figure, the dislocation distribution diagrams of aluminum-magnesium-silicon alloy samples under different heat treatment methods are as follows:
[0173]
[0174] Conclusion: Ultrasonic vibration aging treatment significantly accelerates the generation, movement and entanglement of dislocations. After 1 hour of aging, the number of dislocation entanglements increased rapidly. As time went on, the entanglements gradually disintegrated into dislocation lines, and the distribution of dislocations became more uniform. After 3 hours, the dislocation lines became shorter and more dispersed, but their number was still much higher than that of conventional aging treatment. The strengthening effect of ultrasonic vibration on dislocations was significantly better than that of conventional heat treatment methods, especially in terms of the generation rate and density of dislocations. Through the coupling effect of ultrasonic and heat treatment, the internal microstructure of Al-Mg-Si alloy material was rapidly optimized, and the grain refinement, precipitation of strengthening phases and the generation of dislocation entanglements were significantly enhanced. The increase in dislocation density directly improved the hardness and strength of Al-Mg-Si alloy material, making Al-Mg-Si alloy show superior mechanical properties after short aging treatment. Therefore, ultrasonic vibration aging is an effective and efficient treatment method that can significantly improve the comprehensive properties of Al-Mg-Si alloy material.
[0175] Determination of the precipitation of strengthening phases in Al-Mg-Si alloy samples under different heat treatment times and conditions in transmission electron microscopy (TEM) images
[0176] according to Figure 2A set of transmission electron microscopy (TEM) images in the figure show the precipitation of strengthening phases in aluminum-magnesium-silicon alloy samples after different heat treatment times and conditions. A set of transmission electron microscopy (TEM) images in the figure show the precipitation of strengthening phases in aluminum-magnesium-silicon alloy samples after different heat treatment times and conditions.
[0177]
[0178] Conclusion: Pass Figure 2 From the analysis, it can be concluded that ultrasonic vibration aging is an effective strengthening method, which can significantly accelerate the precipitation of β" phase in aluminum-magnesium-silicon alloy. Especially after 3 hours of ultrasonic vibration aging, the amount and distribution of β" phase reached the optimal state, significantly improving the mechanical properties of aluminum-magnesium-silicon alloy rods. Compared with aluminum-magnesium-silicon alloy rod samples with conventional aging for 3 hours, ultrasonic vibration can improve the precipitation efficiency of the strengthening phase in a shorter time and accelerate the strengthening effect. This shows that ultrasonic vibration can shorten the aging time and enhance the precipitation of β" phase, which has significant advantages in improving the performance of aluminum-magnesium-silicon alloy rods.
[0179] Determination of the hardness of aluminum-magnesium-silicon alloy bar samples by different heat treatment methods
[0180] Figure 3 The effects of different heat treatment methods on the hardness of aluminum-magnesium-silicon alloy are shown, and the effects of ultrasonic vibration aging and conventional aging on the hardness of aluminum-magnesium-silicon alloy bars at different treatment times are compared. This figure mainly reflects the change trend of the hardness of aluminum-magnesium-silicon alloy bars as the aging time increases. Figure 3 In the figure, the X-axis (horizontal axis) represents the aging treatment time (hours); the Y-axis (vertical axis) represents the Vickers hardness (HV), which is used to measure the hardness of the aluminum-magnesium-silicon alloy rod.
[0181] like Figure 3 As shown in the figure, the red dotted line (ultrasonic vibration aging) indicates that ultrasonic vibration aging treatment can significantly improve the hardness of the aluminum-magnesium-silicon alloy rod; and the hardness increases rapidly with the increase of aging time, especially at 3 hours, the hardness reaches about 125HV. This trend shows that ultrasonic vibration aging enhances the hardness of the aluminum-magnesium-silicon alloy rod by accelerating the precipitation of strengthening phases, increasing dislocation density and refining grains. Ultrasonic vibration can effectively improve the hardness in a relatively short time, especially at 1 hour and 2 hours, it also shows a significant increase in hardness, reaching about 105HV and 115HV respectively.
[0182] like Figure 3As shown in the figure, the black dotted line (conventional aging) indicates that conventional aging treatment also improves the hardness of the aluminum-magnesium-silicon alloy rod, but the increase is not as obvious as ultrasonic vibration aging; the hardness gradually increases with time, and the hardness only reaches about 109HV at 3 hours. This trend shows that compared with ultrasonic vibration aging, the hardness of conventional aging increases slowly, and the hardness level of ultrasonic vibration aging cannot be reached in the same time. This is because the precipitation rate of the strengthening phase in conventional aging is slow, and the dislocation proliferation and grain refinement are not as effective as ultrasonic vibration aging, resulting in less hardness growth.
[0183] therefore, Figure 3 It is clearly shown that ultrasonic vibration aging treatment can significantly improve the hardness of aluminum-magnesium-silicon alloys more than conventional aging treatment, and ultrasonic vibration aging can achieve higher hardness values in a shorter time. This treatment method improves the comprehensive mechanical properties of aluminum-magnesium-silicon alloys by accelerating the precipitation of strengthening phases, increasing dislocation density and promoting grain refinement.
[0184] Summary: Ultrasonic vibration aging can significantly improve the hardness of aluminum-magnesium-silicon alloy in a relatively short period of time, and the hardness value is much higher than the hardness of conventional aging treatment, especially at 3 hours, the hardness of ultrasonic vibration aging is about 14.7% higher than that of conventional aging. The superiority of ultrasonic vibration aging is reflected in the acceleration of microstructural changes such as precipitation of strengthening phases, increase of dislocation density and grain refinement, thereby significantly improving the comprehensive performance of aluminum-magnesium-silicon alloy materials. Therefore, ultrasonic vibration aging significantly improves the comprehensive mechanical properties of aluminum-magnesium-silicon alloy by accelerating the precipitation of strengthening phases, increasing dislocation density and grain refinement. Within the same aging time, the effect of ultrasonic vibration aging treatment is far better than conventional aging, and higher hardness and strength can be achieved in a shorter time, which makes ultrasonic vibration aging an efficient strengthening treatment method for aluminum-magnesium-silicon alloys.
[0185] Determination of grain morphology and grain size of aluminum-magnesium-silicon alloy under different treatment conditions
[0186] Figure 4 The microstructure morphology and grain size changes of aluminum-magnesium-silicon alloy samples in the solid solution state and after ultrasonic vibration aging at 150°C for 1-3h are shown. With the increase of ultrasonic vibration aging time, the grains gradually become finer and the microstructure also changes significantly. This is a set of electron backscatter diffraction (EBSD) images showing the grain morphology and size of aluminum-magnesium-silicon alloys under different treatment states. The images show the microstructural evolution of aluminum-magnesium-silicon alloys, focusing on the comparison of grain refinement in the solid solution state and after ultrasonic vibration aging treatment for different times; the grain size of each sub-image is represented by a histogram and the average grain size (d).
[0187]
[0188]
[0189] Under different treatment conditions, the main characteristics of the grain morphology and grain size of the aluminum-magnesium-silicon alloy are as follows: from the strip structure, the strip structures in all images are arranged along the extrusion direction (ED direction), showing the deformation structure formed by the aluminum-magnesium-silicon alloy during the extrusion process. Although the grains are constantly refined and rearranged in orientation, the strip structure morphology remains stable during the ultrasonic vibration aging treatment, indicating that the strip structure is mainly affected by the extrusion method, while the ultrasonic vibration mainly affects the microstructure and arrangement of the grains; from the grain refinement, with the extension of the ultrasonic vibration aging time, the grain size inside the aluminum-magnesium-silicon alloy continues to decrease, from 10.24μm in the solid solution state to 6.49μm. The mechanical stress induced by ultrasonic vibration accelerates grain refinement and significantly improves the microstructure of the aluminum-magnesium-silicon alloy; from the adjustment of grain orientation, ultrasonic vibration aging also promotes the gradual consistency of grain orientation. Under the high-frequency excitation stress of ultrasonic vibration, the grains inside the aluminum-magnesium-silicon alloy rotate and gradually tend to the same or similar orientation. Especially after aging for 3 hours, the orientation of the grains is basically consistent, indicating that ultrasonic vibration has the ability to adjust the grain orientation.
[0190] Conclusion: Ultrasonic vibration aging treatment can not only significantly refine the grains, but also adjust the grain orientation to make the structure more uniform and orderly. With the extension of aging time, the grain size gradually decreases and the grain orientation tends to be consistent. These microstructural improvements will have a substantial positive effect on the mechanical properties of aluminum-magnesium-silicon alloys, such as strength, hardness and fatigue resistance.
[0191] Determination of the tensile strength of aluminum-magnesium-silicon alloy by 5 different heat treatment methods
[0192] Figure 5 The effects of different heat treatment methods on the tensile strength of aluminum-magnesium-silicon alloy are shown, with a focus on comparing the changes in tensile strength of ultrasonic vibration aging and conventional aging at different aging times. The following chart illustrates the effects of different heat treatment methods on the tensile strength of aluminum-magnesium-silicon alloy.
[0193]
[0194]
[0195] like Figure 5As shown in the figure, the red dotted line (ultrasonic vibration aging) indicates that the tensile strength increases significantly with the extension of aging time; under ultrasonic vibration aging treatment, the tensile strength of the aluminum-magnesium-silicon alloy increases rapidly within 1 hour, reaching 317MPa; this indicates that ultrasonic vibration accelerates the precipitation of strengthening phases (such as β" phase), and the mechanical properties of the aluminum-magnesium-silicon alloy are significantly enhanced due to the dislocation proliferation and grain refinement caused by vibration. As the aging time is extended to 3 hours, the tensile strength further increases, reaching a maximum value of 334MPa, which indicates that under the combined action of ultrasonic vibration and heat treatment, the strengthening effect continues to increase, and the optimization process of the microstructure, such as the precipitation of strengthening phases and dislocation entanglement, continues.
[0196] Conclusion: Although conventional aging treatment can also improve tensile strength, the strengthening effect is obviously not as good as ultrasonic vibration aging in a shorter time (1-3 hours), which means that ultrasonic vibration aging has higher efficiency and better strengthening effect in industrial applications. Therefore, ultrasonic vibration aging treatment is a more efficient strengthening method that can significantly improve the tensile strength of aluminum-magnesium-silicon alloy in a shorter time and is suitable for industrial applications with high requirements for mechanical properties.
[0197] The results of the hardness comparison under 6 different ultrasonic vibration aging temperatures
[0198] Figure 6 The trend of the Vickers hardness (HV) of aluminum-magnesium-silicon alloy changing with aging time (hours) at different ultrasonic vibration aging temperatures (130℃, 150℃, 170℃) is shown in the following chart.
[0199]
[0200]
[0201] Comparative analysis of hardness under different ultrasonic vibration aging temperatures:
[0202] When the aging temperature is 130℃, although the premature phase transformation is avoided, the strengthening effect is weak due to the low temperature. After aging for 4 hours, the hardness is only increased to about 115HV, and the strengthening effect is limited.
[0203] When the aging temperature is 150℃, the best aging effect is shown, and the stable precipitation of β" phase is ensured for a long time. The hardness reaches 125HV after 3 hours, which is the most ideal temperature for strengthening effect.
[0204] When the aging temperature is 170℃, the initial strengthening effect is rapid, but the high temperature causes the β" phase to transform into β' phase and β phase prematurely. The hardness decreases after 3 hours and finally stabilizes at around 115HV. The strengthening effect is far less significant than that under 150℃ conditions.
[0205] Comparison of hardness at different ultrasonic vibration aging temperatures: Based on the three ultrasonic vibration aging temperatures, the hardness of the sample increases slowly when aged at 150°C, because the β" phase precipitates in an orderly manner at this temperature, and the β" phase will not transform into the β' phase and β phase in a short time at 150°C. Therefore, after 3 hours of ultrasonic vibration aging, its hardness increases to 125HV. If the ultrasonic vibration aging time continues to increase, the β" phase in the matrix will transform, resulting in a decrease in the hardness of the aluminum-magnesium-silicon alloy.
[0206] The ultrasonic aging vibration device described in the present invention is composed of six parts: an ultrasonic generator 1, a transducer 2, a horn 3, a drying box 4, a fixed base 5 and a fixed frame 6; the ultrasonic generator 1 can convert an electrical signal into an ultrasonic signal; the transducer 2 can convert the received ultrasonic signal into a mechanical vibration with the same frequency. The lower end of the transducer 2 has a horn 3 for amplifying the mechanical vibration amplitude. The aluminum alloy rod is connected to the horn 3 and fixed in a drying box 4 with a fixed temperature; the horn 3 is used to amplify the mechanical vibration amplitude generated by the transducer 2 to ensure that the aluminum alloy rod It can withstand sufficiently strong mechanical vibration; the drying box 4 can maintain the temperature stability during the aging process; the fixed base 5 is used to support the aluminum-magnesium-silicon alloy rod to ensure that the rod remains stable during mechanical vibration and heat treatment, avoid displacement or shaking during vibration, and ensure that the vibration can be evenly transmitted to the entire aluminum-magnesium-silicon alloy rod; the fixed frame 6 can ensure that when the vibration is transmitted from the amplitude rod 3 to the aluminum-magnesium-silicon alloy rod, the ultrasonic vibration can be more effectively transmitted to the entire aluminum-magnesium-silicon alloy rod to enhance the uniformity of mechanical vibration inside the aluminum-magnesium-silicon alloy rod, thereby improving the vibration efficiency.
[0207] The specific parameters of the six parts of the ultrasonic aging vibration device described in the present invention are as follows:
[0208]
[0209]
[0210] Example 4 A laboratory implementation method of treating aluminum-magnesium-silicon alloy bars using an ultrasonic aging vibration device
[0211] In a specific embodiment, an ultrasonic aging vibration device is used to complete the short aging treatment of an aluminum-magnesium-silicon alloy bar. The coupling effect of ultrasonic vibration and heat treatment effectively accelerates dislocation movement and strengthening phase precipitation, and significantly refines the grains.
[0212] The equipment used in this embodiment is an ultrasonic aging vibration device, which is composed of an ultrasonic generator 1, a transducer 2, a horn 3, a drying box 4, a fixed base 5, and a fixed frame 6. The aluminum alloy material used in this embodiment is a hot extruded aluminum-magnesium-silicon alloy rod with a length of 25 cm and a diameter of 12 mm.
[0213] In a specific embodiment, it is necessary to carry out pre-treatment of ultrasonic coupled short-aging treatment, which are material cleaning, solution treatment and water-cooled quenching. Specifically, in the material cleaning stage, the aluminum-magnesium-silicon alloy rod needs to be prepared, and the surface of the aluminum-magnesium-silicon alloy rod needs to be cleaned to ensure that there is no oil and oxide to avoid affecting the effect of the solution treatment; in the solution treatment stage, the aluminum-magnesium-silicon alloy rod needs to be placed in a tubular furnace preheated to 555°C and kept for 1 hour. The purpose of this process is to fully dissolve the second phase (such as Mg2Si and AlFeMnSi) in the aluminum-magnesium-silicon alloy rod into the aluminum matrix to form a uniform supersaturated solid solution; in the water-cooled quenching stage, the aluminum-magnesium-silicon alloy rod is taken out immediately after the solution treatment is completed, and quickly placed in a water tank with a water temperature of 20°C for quenching. Rapid cooling allows the aluminum-magnesium-silicon alloy rod to maintain a high degree of solid solution state to prevent the precipitation phase from precipitating prematurely.
[0214] In this embodiment, the ultrasonic aging vibration device needs to be assembled and prepared. The specific installation steps are as follows:
[0215] S1. Install the ultrasonic generator 1: fix the ultrasonic generator 1 at the top of the ultrasonic aging vibration device; the ultrasonic generator 1 is the core part of the ultrasonic aging vibration device, responsible for converting electrical signals into ultrasonic signals; connect the ultrasonic generator 1 to the transducer 2 through a cable to ensure smooth signal transmission;
[0216] S2. The transducer 2 is connected to the horn 3: The transducer 2 receives the signal from the ultrasonic generator and converts the ultrasonic signal into mechanical vibration. It is important to ensure that the transducer 2 and the horn 3 are firmly connected through a threaded connection or a locking structure to ensure that the mechanical vibration can be effectively transmitted to the horn 3;
[0217] S3. The horn 3 is connected to the aluminum-magnesium-silicon alloy rod: The function of the horn 3 is to amplify the amplitude of the mechanical vibration to ensure that the mechanical vibration is strong enough to act on the aluminum-magnesium-silicon alloy rod; in this process, the upper end of the aluminum-magnesium-silicon alloy rod is connected to the horn 3 by threads or fasteners; a tight connection is ensured to ensure that the mechanical vibration is transmitted to the aluminum-magnesium-silicon alloy rod without hindrance;
[0218] S4. Preparation of drying oven 4: Set the temperature of drying oven 4 to 150°C to ensure constant temperature treatment; drying oven 4 is a key equipment in the entire heat treatment process, and can maintain the temperature stability of the aluminum-magnesium-silicon alloy rod during aging treatment; drying oven 4 is placed at the lower position of the ultrasonic aging vibration device, and can surround the middle and lower part of the aluminum-magnesium-silicon alloy rod; and the middle and lower part of the aluminum-magnesium-silicon alloy rod enters the drying oven 4, ensuring that the heat treatment and mechanical vibration are carried out simultaneously to form a coupling field;
[0219] S5. Installation of the fixed frame 6: The fixed frame 6 is installed in the middle and upper part of the aluminum-magnesium-silicon alloy rod, and the function of the fixed frame 6 is to prevent the aluminum-magnesium-silicon alloy rod from lateral shaking during the mechanical vibration process, which will affect the uniformity of the vibration; through the fixed frame 6, the aluminum-magnesium-silicon alloy rod remains stable during the vibration process, and it can ensure that the vibration is evenly transmitted to each part of the aluminum-magnesium-silicon alloy rod, avoiding the loss of vibration energy;
[0220] S6. Installation of the fixed base 5: The lower end of the aluminum-magnesium-silicon alloy rod is placed on the fixed base 5 by gravity; the fixed base is located at the bottom of the ultrasonic aging vibration device to provide stable support to ensure that the aluminum-magnesium-silicon alloy rod will not be displaced or shaken during the vibration and heat treatment process; the fixed base 5 needs to ensure that the lower end of the aluminum-magnesium-silicon alloy rod can maintain longitudinal free vibration, so that the mechanical vibration can be transmitted to the entire aluminum-magnesium-silicon alloy rod through the amplitude transformer 3.
[0221] In this embodiment, an ultrasonic aging vibration device is used to perform ultrasonic aging vibration treatment on the aluminum-magnesium-silicon alloy rod, and the specific steps are as follows:
[0222] S1. Ultrasonic signal generation: start the ultrasonic generator 1 to generate a high-frequency ultrasonic signal with a frequency of 20kHz; the ultrasonic generator 1 converts the electrical signal into an ultrasonic signal and transmits it to the transducer 2 through a cable;
[0223] S2. Mechanical vibration conversion: First, after receiving the ultrasonic signal, the transducer 2 converts the signal into mechanical vibration of the same frequency; mechanical vibration conversion is the core step of ultrasonic aging vibration, which acts on the internal structure of the aluminum-magnesium-silicon alloy rod through mechanical vibration;
[0224] S3. Vibration amplification and transmission: The horn 3 amplifies the mechanical vibration generated by the transducer 2 to ensure that the vibration has sufficient amplitude and can be effectively transmitted to the aluminum-magnesium-silicon alloy rod; then, through the amplification effect of the horn 3, the mechanical vibration is evenly transmitted to the aluminum-magnesium-silicon alloy rod; at this time, the aluminum-magnesium-silicon alloy rod begins to undergo microstructural changes under the combined effects of mechanical vibration and heat treatment;
[0225] S4. Thermal coupling treatment: while mechanical vibration is being performed, the drying oven 4 provides a constant 150°C thermal field, forming a coupling field of mechanical vibration and thermal field; mechanical vibration can promote the dislocation movement inside the aluminum-magnesium-silicon alloy rod, while heat treatment is conducive to the precipitation of strengthening phases. The synchronous action of mechanical vibration and heat treatment accelerates the improvement of the performance of the aluminum-magnesium-silicon alloy rod;
[0226] S5. Aging treatment time: The treatment time is set to 2 hours. During this period, mechanical vibration and heat treatment work together, and the strengthening phase (such as β" phase) can precipitate quickly, and the dislocation density increases significantly. During the aging process, the grain refinement effect is obvious, the internal structure of the aluminum-magnesium-silicon alloy rod is gradually optimized, and the mechanical properties are significantly improved.
[0227] S6. Cooling after ultrasonic aging vibration: turn off the ultrasonic generator 1 and the drying oven 4; after the treatment is completed, stop the ultrasonic vibration and turn off the heating system of the drying oven 4; and then the treated aluminum-magnesium-silicon alloy rod needs to be cooled to room temperature; in this process, avoid rapid cooling to prevent thermal stress or cracks from occurring inside the aluminum-magnesium-silicon alloy rod;
[0228] S7. Remove the rod: When the aluminum-magnesium-silicon alloy rod is cooled to room temperature, the aluminum-magnesium-silicon alloy rod is removed from the drying oven 4 and the fixed base 5 to prepare for subsequent microstructure observation and performance testing;
[0229] S8. Microstructure observation and testing after ultrasonic aging treatment:
[0230] 1) Microstructure observation: Samples were taken from the treated aluminum-magnesium-silicon alloy bars, and mechanical grinding and electrolytic double spraying were performed to observe their microstructures;
[0231] 2) Microstructure analysis: The microstructure of the aluminum-magnesium-silicon alloy rod sample was observed by transmission electron microscopy (TEM), especially the precipitation of the strengthening phase (such as β" phase) and the grain refinement effect; ultrasonic vibration promoted the increase of dislocation density and accelerated the precipitation of the strengthening phase;
[0232] 3) Hardness test: Vickers hardness test was performed to compare the hardness changes of the aluminum-magnesium-silicon alloy bar samples before and after treatment; the results showed that the hardness of the aluminum-magnesium-silicon alloy bar samples increased by 20%-30% after treatment;
[0233] 4) Tensile strength test: The yield strength and tensile strength of the aluminum-magnesium-silicon alloy bar samples were tested. After ultrasonic aging treatment, the yield strength and tensile strength of the aluminum-magnesium-silicon alloy bar samples were significantly improved;
[0234] 5) Fatigue performance test: Through fatigue testing, it was found that the fatigue resistance of the treated aluminum-magnesium-silicon alloy bar samples was greatly improved, and the fatigue life was extended by 20%-25%.
[0235] Conclusion: Through the implementation method of the ultrasonic aging vibration device mentioned above, the hot extruded aluminum-magnesium-silicon alloy rods were successfully and efficiently treated. The treated aluminum-magnesium-silicon alloy rod samples showed significant microstructure optimization effects such as grain refinement, accelerated precipitation of strengthening phases, and increased dislocation density, which significantly improved the hardness, tensile strength and fatigue properties of the aluminum-magnesium-silicon alloy rod samples. The ultrasonic aging vibration device provides an efficient and innovative solution for the short-term aging treatment of high-strength aluminum alloys, and is widely used in engineering applications that require high strength and high fatigue resistance.
[0236] Example 5: Implementation method of a heat treatment workshop for treating aluminum-magnesium-silicon alloy bars using an ultrasonic aging vibration device
[0237] In a specific embodiment, the aluminum-magnesium-silicon alloy rod is treated by an ultrasonic aging vibration device, and the rapid precipitation of the strengthening phase, grain refinement and increase of dislocation density are achieved in the heat treatment workshop, thereby significantly improving the mechanical properties of the aluminum-magnesium-silicon alloy rod. In particular, the treated aluminum alloy has been significantly improved in terms of hardness, tensile strength, yield strength and fatigue life. The coupled field of ultrasound and heat treatment provides an efficient strengthening method for aluminum-magnesium-silicon alloy rods, which is suitable for engineering applications with high requirements for high strength and fatigue resistance.
[0238] The equipment used in this embodiment is an ultrasonic aging vibration device, which is composed of an ultrasonic generator 1, a transducer 2, a horn 3, a drying box 4, a fixed base 5, and a fixed frame 6. The aluminum alloy material used in this embodiment is a hot extruded aluminum-magnesium-silicon alloy rod with a length of 25 cm and a diameter of 12 mm. The site of this embodiment is a heat treatment workshop equipped with power supply, temperature control equipment, ultrasonic equipment, and a safe operation area.
[0239] In a specific embodiment, preparation of a heat treatment workshop is required. The heat treatment workshop requires power supply to ensure that there is a stable three-phase power supply in the workshop to provide sufficient power for the ultrasonic generator 1, the transducer 2 and the heating equipment. The heat treatment workshop requires a ventilation system to ensure that hot air can be discharged in time during the heating and cooling process to avoid damage to the equipment or environment caused by overheating. In the heat treatment workshop, the ultrasonic aging vibration device should be installed on a special operating table in the workshop; the operating table should have a good support structure to ensure the stability of the ultrasonic aging vibration device during operation. The heat treatment workshop needs to prepare temperature control equipment, and the heating element in the drying box 4 needs to be connected to the temperature control system of the workshop to ensure that the temperature can be kept constant. The heat treatment workshop needs to be safely prepared. Due to the use of the ultrasonic generator 1 and the heating equipment, an isolation fence should be set in the operating area to ensure the safety of personnel. The operator should wear protective gloves and goggles. The heat treatment workshop needs to be equipped with fire extinguishers and emergency power-off equipment to deal with possible safety hazards.
[0240] In this embodiment, the ultrasonic aging vibration device needs to be assembled and prepared. The specific installation steps are as follows:
[0241] S1. Installation of ultrasonic generator 1: Fix the ultrasonic generator 1 on the top of the operating table in the workshop, ensure that the equipment is stable and connected to the power supply of the workshop;
[0242] S2. Installation of transducer 2 and horn 3: Fix transducer 2 below ultrasonic generator 1, and ensure that transducer 2 and horn 3 are firmly connected through threads; horn 3 is used to amplify the amplitude of mechanical vibration and should be firmly connected to the upper end of aluminum-magnesium-silicon alloy rod;
[0243] S3. Drying oven 4 is set: the drying oven 4 is placed at the bottom of the operating table of the ultrasonic aging vibration device, and the temperature control system of the drying oven 4 is connected to the temperature control equipment of the workshop, and the temperature is set to 150 ° C to provide a stable thermal field for aging treatment;
[0244] S4. Installation of the fixed frame 6: A fixed frame 6 is installed in the upper middle portion of the aluminum-magnesium-silicon alloy rod to limit the lateral shaking of the rod that is prone to occur during vibration;
[0245] S5. Installation of the fixed base 5: The fixed base 5 is placed at the bottom of the operating table of the ultrasonic aging vibration device to support the lower end of the aluminum-magnesium-silicon alloy rod to ensure the stability of the rod during the vibration process;
[0246] S6. Temperature control setting of drying oven 4: Set the temperature of drying oven 4 to 150°C and connect it to the workshop temperature control system to ensure that the temperature remains stable during the processing;
[0247] S7. Environmental monitoring: Use the temperature and humidity monitoring equipment in the workshop to ensure that the operating environment is suitable and avoid adverse effects of external conditions on the operation of the equipment.
[0248] In this embodiment, an ultrasonic aging vibration device is used to perform ultrasonic aging vibration treatment on the aluminum-magnesium-silicon alloy rod, and the specific steps are as follows:
[0249] S1. Material cleaning and preparation: Select hot extruded aluminum-magnesium-silicon alloy bars with no oil or impurities on the surface to ensure the efficiency of aging treatment. The bar specifications are 25cm in length and 12mm in diameter;
[0250] S2. Solution treatment operation: the aluminum-magnesium-silicon alloy rod is placed in a tube furnace preheated to 555°C for 1 hour to ensure that the second phase in the matrix is fully dissolved to form a uniform supersaturated solid solution;
[0251] S3. Water-cooling quenching: After the solution treatment, the aluminum-magnesium-silicon alloy rod is immediately taken out of the tube furnace and placed in a water tank with a water temperature of about 20°C for rapid cooling to prevent the premature precipitation of the precipitated phase;
[0252] S4. Ultrasonic signal generation: start the ultrasonic generator 1, set the signal frequency to 20kHz, generate a high-frequency ultrasonic signal, and transmit it to the transducer 2 through the cable;
[0253] S5. Mechanical vibration conversion: The transducer 2 converts the ultrasonic signal into mechanical vibration of the same frequency, and the vibration is transmitted to the aluminum-magnesium-silicon alloy rod through the horn 3;
[0254] S6. Vibration amplification and transmission: The horn 3 amplifies the mechanical vibration amplitude and transmits it evenly to the aluminum-magnesium-silicon alloy rod to ensure that the vibration intensity can promote microstructural changes;
[0255] S7. Heating of drying oven 4: The temperature in drying oven 4 is stably maintained at 150°C to ensure that the aluminum-magnesium-silicon alloy rod is heat treated in a mechanical vibration and constant temperature environment; the temperature control system of drying oven 4 ensures a constant temperature throughout the process;
[0256] S8. Aging treatment time: Maintain the coupling of mechanical vibration and heat treatment for 2 hours, during which the strengthening phase (such as β" phase) precipitates rapidly and the dislocation density increases significantly; use the workshop monitoring system to observe the working condition of the device to ensure that the vibration is evenly transmitted and the temperature remains stable;
[0257] S9. Turn off the equipment: After the aging treatment is completed, turn off the ultrasonic generator 1 and the drying oven 4 in turn, and stop the mechanical vibration and heating;
[0258] S10. Natural cooling: The treated aluminum-magnesium-silicon alloy bars need to be naturally cooled to room temperature. The workshop should maintain air circulation to avoid thermal stress caused by rapid cooling.
[0259] S11. Taking out the rod: After cooling, the aluminum-magnesium-silicon alloy rod is taken out from the fixed base 5 and the drying oven 4 to prepare for performance testing and microstructure observation.
[0260] Implementation effect and summary: Through the implementation of the ultrasonic aging vibration device in the workshop, the short-aging treatment of the aluminum-magnesium-silicon alloy rods has achieved remarkable results. The ultrasonic aging vibration device combines the coupling effect of ultrasonic vibration and constant thermal field, which greatly accelerates the optimization of the internal microstructure of the aluminum-magnesium-silicon alloy rods. Specifically, the rapid precipitation of the strengthening phase β" phase improves the strength and hardness of the aluminum-magnesium-silicon alloy rods. Ultrasonic vibration promotes the proliferation and movement of dislocations, refines the grains, and improves the plasticity and fatigue resistance of the aluminum-magnesium-silicon alloy rods. The coupling of mechanical vibration and heat treatment accelerates the refinement of grains and makes the microstructure of the aluminum-magnesium-silicon alloy rods more uniform and stable. This method, which combines ultrasonic vibration and short-aging treatment, realizes an efficient processing process in the workshop, saves time, and improves the performance of aluminum-magnesium-silicon alloy rods. It is suitable for use in engineering structures that require high strength and fatigue resistance.
Claims
1. A method for ultrasonic vibration thermal aging treatment of aluminum-magnesium-silicon alloy, characterized in that: The following phases are included: 1). Solution treatment: The coarse second phase in the rod-shaped aluminum-magnesium-silicon alloy matrix is fully dissolved at high temperature to form a supersaturated solid solution; 2). Water-cooling quenching: through rapid cooling, the formation of precipitation phase is prevented and the rod-shaped aluminum-magnesium-silicon alloy material is kept in a highly solid solution state after solution treatment; 3). Thermal aging treatment of ultrasonic mechanical vibration, including: 3.1 Heating treatment period: Ultrasonic mechanical vibration is introduced during the heating process at 130℃-170℃ for 1-3 hours to form a coupled field of temperature + mechanical vibration, regulate the generation and movement of dislocations, and further improve the microstructural properties of rod-shaped aluminum-magnesium-silicon alloy materials; 3.2 Thermal aging treatment period: Through 1-3 hours, 130℃-170℃ thermal aging treatment, the maximum precipitation of β" strengthening phase is promoted, and the dislocation density is controlled by combining ultrasonic mechanical vibration to achieve microstructure optimization; 3.3 Short-time coupling treatment: Through 1-3 hours, 130℃-170℃ short-time coupling treatment, under the action of temperature and ultrasonic mechanical vibration, the dislocation density is regulated and the microstructure of the aluminum-magnesium-silicon alloy material is optimized.
2. The method for ultrasonic vibration heat aging treatment of aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The step of introducing ultrasonic mechanical vibration and performing a heating treatment comprises the following steps: S1. Mechanical connection: Select aluminum-magnesium-silicon alloy rods that have been water-cooled and quenched to ensure that the ultrasonic transducer (2) can be firmly connected to the aluminum-magnesium-silicon alloy rod and the vibration is evenly transmitted; S2. Surface cleaning: Ensure that the surface of the aluminum-magnesium-silicon alloy bar is clean and free of oxides or dirt; S3. Prepare an ultrasonic aging vibration device: select an ultrasonic generator (1) with a power of 100 W and a frequency of 20 kHz and check the status, connect the ultrasonic transducer (2), and ensure that the transducer is intact and the frequency is consistent; before the thermal aging treatment, check all cables and interface connections to ensure that the signal transmission is normal; S4. Prepare an ultrasonic aging vibration device for heating treatment: first preheat the drying oven (4) to 150 ℃ in advance to ensure uniformity of heat conduction; S5. Install, fix and connect the ultrasonic aging vibration device; S6. The drying oven (4) is heated and ultrasonic vibration is introduced simultaneously: when the drying oven (4) is heated to 150°C, the ultrasonic generator (1) is started at the same time to vibrate the aluminum-magnesium-silicon alloy rod at a frequency of 20kHz, and the heating and vibration synchronous treatment is continued for 3 hours to ensure the maximum precipitation of the strengthening phase and to regulate the dislocation by vibration; S7. Naturally cooled aluminum-magnesium-silicon alloy rods.
3. The method for ultrasonic vibration heat aging treatment of aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The thermal aging treatment period includes the following steps: S1. Preparation for aging treatment: Using water-cooled quenched aluminum-magnesium-silicon alloy rods connected to an ultrasonic transducer (2), preheat the drying oven (4) to 150°C; check the ultrasonic generator (1) and the transducer (2) to ensure that the equipment power is 100W and the frequency is 20kHz, and confirm that the vibration transmission is unimpeded; combine the thermal aging at 150°C with the 20kHz ultrasonic vibration to form a stable coupling field, and quickly complete the dislocation regulation and strengthening phase precipitation; S2. Aging treatment: Place the aluminum-magnesium-silicon alloy rod in a drying oven (4), ensure that one end of the rod is connected to a fixed base (5) in the drying oven (4), and the other end is tightly connected to an external ultrasonic transducer (2); S3 insulation treatment: keep the internal temperature of the drying oven (4) constant at 150 ℃, carry out aging insulation treatment for 3 hours to ensure that the β "strengthening phase is fully precipitated and the dislocation density reaches the ideal microstructure adjustment; S4. Introducing synchronous ultrasonic vibration: During the heating aging process at 150°C, the ultrasonic generator (1) is started to introduce ultrasonic mechanical vibration at a frequency of 20kHz to ensure that the ultrasonic transducer (2) evenly transmits the vibration to the aluminum-magnesium-silicon alloy rod; S5. Coupling field formation: Under the action of thermal aging treatment and ultrasonic vibration, a coupling field of temperature + mechanical vibration is formed, which promotes the generation and redistribution of dislocations and optimizes the dislocation density. Finally, the coupling field causes the β" phase in the aluminum-magnesium-silicon alloy to precipitate to the maximum extent. Due to the low aging temperature (150℃), the conversion rate of β" to β′ or β phase is reduced, ensuring that the β" phase is fully precipitated to achieve the best strengthening effect. S6. Thermal aging treatment monitoring; S7. Natural cooling: Place the aluminum-magnesium-silicon alloy rod in a room temperature environment to cool naturally to avoid stress concentration or material cracking of the aluminum-magnesium-silicon alloy rod caused by rapid cooling.
4. The method for ultrasonic vibration heat aging treatment of aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The short-term coupling processing period includes the following usage methods: S1. Control the coupling treatment time between 1-3 hours to prevent excessive increase in dislocation density and ensure the precipitation of strengthening phase; S2. Vibration frequency and intensity control: The vibration frequency of the ultrasonic generator (1) is set to be maintained at 20 kHz; S3. Cool naturally for 1-2 hours to ensure that the surface and interior of the aluminum-magnesium-silicon alloy bar are evenly cooled to room temperature.
5. The method for ultrasonic vibration heat aging treatment of aluminum-magnesium-silicon alloy according to claim 1, characterized in that: Before subjecting the aluminum-magnesium-silicon alloy rod to thermal aging treatment, a solid solution treatment is also performed, and the solid solution treatment includes the following steps: S1. Aluminum material preparation and pretreatment: Select the rod-shaped aluminum-magnesium-silicon alloy material that has been hot extruded, and ensure that the surface of the rod-shaped aluminum-magnesium-silicon alloy material is clean, without oil stains, oxide layers or impurities; S2. Tube furnace setting: Use a tube furnace for solution treatment, and keep the temperature in the tube furnace at 555℃ to avoid excessive temperature fluctuations; S3. Start of solution treatment: When the furnace temperature reaches 555°C stably, the aluminum-magnesium-silicon alloy rods are quickly placed in the tubular furnace; the aluminum-magnesium-silicon alloy rods must be located in the center of the furnace chamber to ensure that the aluminum-magnesium-silicon alloy rods are evenly heated; S4. Solution treatment and insulation: The Al-Mg-Si alloy bars in the tube furnace need to be kept at 555°C for 1 hour to ensure that all coarse second phases in the alloy matrix are fully dissolved.
6. The method for ultrasonic vibration heat aging treatment of aluminum-magnesium-silicon alloy according to claim 1, characterized in that: Before the aluminum-magnesium-silicon alloy bar is subjected to heat aging treatment, water cooling quenching is also performed, including the following steps: S1. Cooling pretreatment: After the solution treatment, the aluminum-magnesium-silicon alloy should be quenched immediately; first prepare a water-cooled quenching tank and ensure that there is enough water in the tank to completely cover the aluminum-magnesium-silicon alloy rod; S2. Adjust the water temperature: control the water temperature in the quenching tank at 20°C; S3. Quenching operation: One hour after the solution treatment is completed, the heated aluminum-magnesium-silicon alloy rod is quickly taken out from the tube furnace; the aluminum-magnesium-silicon alloy rod at high temperature is immediately placed vertically into a water-cooled quenching tank to ensure that the entire surface of the aluminum-magnesium-silicon alloy rod is evenly in contact with water for cooling; S4. Uniform cooling: The entire aluminum-magnesium-silicon alloy bar is fully cooled to room temperature (about 20°C) in water and kept in water for at least 10-20 minutes; S5. Remove and inspect the aluminum-magnesium-silicon alloy bars for surface quenching cracks, deformation or other surface defects.
7. A method for ultrasonic vibration heat aging treatment of aluminum-magnesium-silicon alloy according to claims 1-6, characterized in that: The optimal ultrasonic vibration aging temperature is 150° C. and the ultrasonic vibration aging time is 3 hours.
8. A high performance aluminum-magnesium-silicon alloy material, characterized in that: The high-performance aluminum-magnesium-silicon alloy material is obtained by the ultrasonic vibration heat aging treatment method of aluminum-magnesium-silicon alloy described in claims 1-6, and the hardness reaches 120-125HV, the tensile strength reaches 320-330MPa, and the average grain size is 6.5-7.0μm.
Citation Information
Cited By
Aluminum alloy and ultrasonic quenching treatment method thereof
CN119913437A
Steam turbine rotor material performance improving process and machining system
CN120818669A
A method for ultrasonic vibration compression regulation of grain boundary precipitate-free zone microstructure of 7xxx series aluminum alloy and application thereof
CN122811592B